A novel antifungal potential protein of Bacillus subtilis-fermented Gracilaria agar-processing wastewater: identification, mechanism, regulation and applications in citrus protection - Zhipeng Li; Miaomiao Yang; Xiaoyu Wei; YanYan Wu; Tao Hong; Yuanfan Yang; Mingjing Zheng; Zedong Jiang; Yanbing Zhu; Qingbiao Li; Hui Ni; Xiping Du (Food Microbiology, 2026)

eIF6 affects the occurrence and development of esophageal cancer - Cong-Gai Huang; Xin Zhou; Ran Huang; Hui-Ling Zhang; Chen-Xi Li; Fei Du; Hong Lei; Qiong Dai; Zhi-Hui Yang (Molecular Biology Reports, 2026)

Influence of soil aeration status on denitrifier gene expression and denitrification gas fluxes (N2O and N2) from repacked pasture soils - Juan Liu; Timothy Clough; Sam Carrick; Jiafa Luo; Andriy Podolyan; Naomi Wells; Jupei Shen; Peng Li; Lianfeng Du; Hong Pan; Limei Zhang; Qiang Zhang; et al. (Soil Biology and Biochemistry, 2026)

Supergravity enrichment coupled with HCl leaching and oxalic acid precipitation for efficient rare earth extraction from Bayan Obo tailings - Jianlong Li; Yan Zhou; Erjun Bu; Xinglu He; Hong Yan; Huayun Du; Yinghui Wei; Xiangxin Xue (Minerals Engineering, 2026)

Impact of nitrogen application rates on nitrogen forms and their distribution in reclaimed soil aggregates: A 7-year study in Northern China - Wuyan Du; Hanqian Wu; Xin Chen; Wenju Guo; Haipeng Li; Yulin Liu; Yi Li; Jie Zhang; Huisheng Meng; Xiangying Wang; Jianping Hong; Minggang Xu; et al. (Agriculture, Ecosystems & Environment, 2026)

Patterns and mechanisms of cross-media antimicrobial resistance development in a typical reclaimed water-receiving urban river - Bang-Ze Li; Shu-Hao Du; Han-Lin Cui; Xin-Xin Gao; Jia-Hao Wu; Bei-Ying Li; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2026)

Mechanical disturbance of trichomes enhances Cd2+ accumulation via malate-mediated stomatal opening in Arabidopsis - Juan Du; Hongyang Wei; Tongxin Shen; Xue Chang; Mingyu Hao; Yang Qi; Ning Liu; Zhiyan Cao; Jingao Dong; Li Hong Zhou (Plant Science, 2026)

The role of peptides in regulating dough quality: A comprehensive review - Chaodong Du; Tingting Hong; Guidong Huang; Xianfeng Zhong; Yue Li; Shuhan Zhang; Liwei Fu; Song Zhu (Food Research International, 2026)

Multiscale protection of anthocyanin via zein/cinnamaldehyde/sodium alginate core-shell nanoparticles enable UV-stabilized colorimetric label for monitoring shrimp and fish freshness - Zhihang Xu; Hong He; Jian Du; Peng Shan; Chenglong Fu; Jinwen Hu; Yehan Tao; Chao Li; Yanna Lv; Haisong Wang (Food Chemistry, 2026)

Enhancing wheat yield through improved sowing uniformity in China: A meta-analysis - Peiyin Jia; Jing-Wei Fan; Xin-Mao Li; Chu-Yi Sun; Jairo A. Palta; Hong Zhao; Wen-Yuan Luo; Lan Yang; Jian Zhang; Feng-Min Li; Yan-Lei Du (Field Crops Research, 2026)

Enhancing bread storage stability with chitosan oligosaccharides of different molecular weights: inhibiting spoilage microorganisms and retarding starch retrogradation - Li-Hong Du; Xiao-Na Guo; Xiao-Hong Sun; Ke-Xue Zhu (Carbohydrate Polymers, 2026)

Herbal residue treatment and return-to-field application: life cycle assessment combined with economic, thermodynamic, and ecological analysis - Qian Deng; Aijun Li; Haoyu Tang; Yongda Huang; Chao Liao; Lianming Du; Yuanyu Zhu; Hong Yao (The International Journal of Life Cycle Assessment, 2026)

Transcriptome and metabolome analysis reveals that cuproptosis in bovine cumulus cells triggers the intercellular transmission of senescence and mitochondrial dysfunction to impair oocyte quality - Hong Xu; Tian Tian; Dan Xu; Xiaoxue Du; Rui Su; Jinghong Liang; Ying Liu; Yuqing Zhang; Chang Liu; Shuang Liang; Qingying Li; Deli Ding; et al. (Theriogenology, 2026)

Technological strategies and land-use dynamics during the Middle Holocene at the Dongguotan site, Northeastern Qinghai-Tibet Plateau - He Honglin; Han Fang; Du Zhanwei; Lü Hongliang; Qiao Hong; Li Jiyuan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

High-throughput nucleic acid extraction using a pipette-tip annular magnetic separator integrated with real-time fluorescent RPA for rapid detection of Burkholderia gladioli pv. cocovenenans - Jiali Wang; Yuting Su; Yaru Chen; Lei Tang; Dongmei Li; Wenchao Du; Yumin Shen; Fangfang Zhou; Hong Duan; Baoguo Sun; Gang Chen; Lingyan Zheng (Food Bioscience, 2026)

Photochemically corrected machine learning framework for real-time VOCs source apportionment in support of air quality management - Yu Han; Xing Peng; Yi Hong; Jiang-Yao Tan; Jiang Wu; Li He; Xiao-Feng Huang; Guang-He Yu; Ke Du (Atmospheric Environment, 2026)

A hierarchical control framework governing the molecular composition and reactivity of dissolved organic matter in subtropical rivers - Guanglong Zhang; Zhenli Guo; Jinfang Du; Yue Ke; Hanyi Li; Mingbao Feng; Jingchun Liu; Haoliang Lu; Xilin Xiao; Hualong Hong; Chongling Yan; Nianzhi Jiao (Science China Earth Sciences, 2026)

Effects of Poly-γ-Glutamic Acid Application on Greenhouse Gas Emissions and GrainYield Under Different Direct-Seeding Methods in Paddy Rice - Rong Huang; Shi-hao Li; Hong-yan Li; Qian Luo; Yu-quan Fu; Qu-chen Zhou; Xiang-yu Huang; Xue-zhu Du; Feng Sheng (Journal of Soil Science and Plant Nutrition, 2026)

Calcium-mediated catalytic ozonation for water purification: Synergistic interplay among surface acid-base sites, alkaline interfacial microenvironment and dynamic oxygen supplementation - Hong-Guang Li; Cheng Chen; Zhi-Hang Wu; Ai-Yong Zhang; Rui-Gang Zhang; Shao-Wei Yuan; Ming Du; Jing-Yu Zhang (Water Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Biallelic hexose-6-phosphate dehydrogenase variants cause mitochondrial dysfunction underlying Parkinson’s disease - Miao Zhao; Yuwen Zhao; Juan Huang; Yu Guo; Wenjun Yu; Haiyan Hou; Yilin Huang; Xinying Du; Yu Zhang; Mujun Xie; Zuowen Ren; Haoyu Guan; et al. (Science Bulletin, 2026)

Acidification associated with plant phosphorus-acquisition strategies decreases nutrient cycling potential of rhizosphere bacteria along the Hailuogou post-glacial chronosequence - Xiao-Long Li; Hongyang Sun; Jun Zhou; Yang Chen; Hong-Qiu Du; Yue-Xin Ming; Shuang Wu; Hans Lambers (Plant and Soil, 2026)
Background and aim Soil nutrient availability, acidification associated with plant phosphorus-mining strategies, and fine root foraging all influence nutrient cycling. However, their relative impacts on microbial nutrient cycling during primary succession remain unclear. Methods We studied a 130-year primary succession along the Hailuogou post-glacial chronosequence in southwest China. Early-successional stages (1–3) are dominated by Hippophae tibetana , which is gradually replaced by Populus purdomii . In the climax community (stage 4), Abies fabri replaces P. purdomii . We collected rhizosphere soil, roots, and leaves from the dominant species, analyzing how phosphorus-acquisition strategies (proxied by soil pH, leaf manganese concentration and fine-root morphology) influenced bacterial nutrient-cycling gene abundance, based on 16S rRNA sequencing. Results Rhizosphere pH and the abundance of genes encoding enzymes involved in ammonium and nitrate assimilation, denitrification and phosphorus mobilization were significantly lower for H. tibetana and A. fabri than for P. purdomii . In contrast, P. purdomii exhibited a significantly higher specific root length. Linear mixed models reveal that leaf manganese concentration was positively correlated with soil acidification. Multiple regression models show that nutrient-cycling potential was more significantly linked to soil pH than to fine-root morphology or soil nutrient availability. Structural equation models indicate that the reduced nutrient-cycling potential was indirectly associated with soil acidification through bacterial co-occurrence networks rather than bacterial richness. Conclusion Soil acidification, associated with phosphorus-mining strategies of H. tibetana and A. fabri , may inhibit microbial nutrient-cycling potential during primary succession. This highlights the interactions between plant nutrient-acquisition strategies and microbial processes in shaping terrestrial nutrient cycling.

Assessing the impact of four tillage methods on soil and water conservation in karst areas of Southwest China: Evidence from a 10-year field study - Quanzhong Sun; Ruyi Zi; Fayong Fang; Bin Yang; Minghai Hong; Yuanze Xu; Lang Peng; Li Qin; Tao Song; Jiaojiao Du; Zhongxian Liu; Zhen Han; et al. (Agriculture, Ecosystems & Environment, 2026)

Topology guided and feature decoupled optical-SAR cross-modal knowledge distillation for rapid post-flood water extent mapping - Yinhaibin Ding; Jingsheng Lei; Yang Li; Lanqing Zhang; Huitao Sun; Yanyan Du; Lu Xu; Hong Zhang (International Journal of Remote Sensing, 2026)

Numerical and experimental study on the soot formation in methane multi-jet flames under microgravity - Wen-Jiao Wang; Kai-Ru Jin; Zhi-Hao Zheng; Hong-Qing Shi; Du Wang; Ling-Nan Wu; Ya-Wen Liu; Longfei Li; Jiayu Sun; Yu Cheng Liu; Zhen-Yu Tian (Fuel, 2026)

Experimental study of thermo-mechanical properties of binary PCM-fiber composite energy piles - Hong Chang; Huicheng Jiang; Yunjie Li; Yuan Du; Xing Wu; Zhaoxuan Wang; Sheng Jiang; Zhengheng Gan (Energy and Buildings, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Zinc-reinforced sandwich-structured nano-magnesium oxide composite collagen barrier membrane for promoting bone regeneration - Hong Du; Shasha Lei; Jianhui Wu; Yiruo He; Lun Yuan; Liming Ge; Changdao Mu; Zhilang Xu; Defu Li (Chemical Engineering Journal, 2026)

Exposure to second-generation flame retardants and risk of metabolic diseases: a systematic review and meta-analysis - Li Shi; Wei Du; Xi-Yuan Peng; Juan Miao; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Zhi-Ren Mu; Hong-Lin Chen (Archives of Toxicology, 2026)

Investigation on Ionospheric TEC disturbances During the Geomagnetic Storms Resulted from ICME Events - Chao Niu; Xiang-yu Li; Xiao-niu Zeng; Hong-ru Li; Ji-hao Liu; Ai-min Du (Applied Geophysics, 2026)

Nitrogen losses, controlling factors, and mitigation potential of global maize and wheat production - Yuqiu Du; Fulu Tao; Yibo Li; Yi Chen; Juan Cao; Hong Zhou; Yifan Shen; Qingran Yang; Jiawei Zhao; Yue Xin (Journal of Cleaner Production, 2026)

Urea as a rising driver of harmful algal blooms: Integrating global patterns, metabolic pathways, and ecological consequences - Huaizhi Qin; Muhamad Syaifudin; Tangcheng Li; Wenkang Fan; Hong Du; Senjie Lin (Harmful Algae, 2026)

Dietary 5-aminolevulinic acid induces strain-specific effects on shell color and innate immunity in Pacific oyster (Crassostrea gigas) through divergent porphyrin metabolism - Biyang Hu; Hong Yu; Chengxun Xu; Lingfeng Kong; Shikai Liu; Shaojun Du; Qi Li (Fish & Shellfish Immunology, 2026)

Heart injury-induced Fibronectin 1 confers liver dysfunction in zebrafish through hepatic Pparβ signaling - Hongbo Lv; Qi Li; Peng Gao; Yanmei Liu; Xiamisiya Tuniyazi; Fen Du; Hong Yu; Ruilin Zhang (Marine Life Science & Technology, 2026)

Functional factors for precision nutrition interventions in starch-based delivery systems - Mengyuan Qin; Lingjin Li; Jing Du; Yan Hong; Zhengbiao Gu; Li Cheng; Zhaofeng Li; Caiming Li; Xiaofeng Ban (Critical Reviews in Food Science and Nutrition, 2026)

Biomass models, allometric relationships, and carbon sink of Sargassum henslowianum in Nan'ao Island - Jing Chen; Jinhuai Ni; Hong Du; Kai Zong; Sunzhaocong Lan; Jianpeng Lu; Dejun Feng; Xu Yang; Guangyang Zhang; Lili Mei; Yuanmin Sun; Xunmeng Li (Regional Studies in Marine Science, 2026)

Silkworm excrement–immobilized bacteria for synergistic remediation of phthalate esters in agricultural soil - Yong-Hong Chen; Huan Du; Ying-Xi Liu; Ke Xu; Jin-Cheng Ye; Bai-Lin Liu; Nai-Xian Feng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Hazardous Materials, 2026)

Advances in the study of unconventional BixMoyOz photocatalysts for energy and environmental applications - Xia Du; Huiqiong Li; Heng Zhang; Tingyu Yao; Hong Yan; Liquan Jing; Jinguang Hu (Journal of Environmental Chemical Engineering, 2026)

Systematic engineering of Bacillus amyloliquefaciens for efficient bovine lactoferrin production - Ying Li; Zhen Li; Suyang Mao; Shanshan Du; Sha Li; Hong Xu; Peng Lei; Yibin Qiu (Food Bioscience, 2026)

Corrigendum to “All-trans-retinoid acid (ATRA) suppresses chondrogenesis of rat primary hind limb bud mesenchymal cells by downregulating p63 and cartilage-specific molecules” [Environ. Toxicol. Pharmacol. 38(2) (2014) 460–468] - Yun-guo Wang; Peng Xie; Yun-gong Wang; Xue-dong Li; Tao-gen Zhang; Zhao-yong Liu; Quan Hong; Shi-xin Du (Environmental Toxicology and Pharmacology, 2026)

Sustainable corecovery of lithium, rubidium, and cesium from lepidolite via calcium chloride–sodium lignosulfonate roasting integrated with precipitation–solvent extraction - Guangyu Duan; Ruiling Du; Guangqian Li; Xin Ma; Zhanfang Cao; Hong Zhong; Shuai Wang (Chemical Engineering Journal, 2026)

Differential responses of soil microbial community structure and function to conventional and biodegradable microplastics - Yuhan Liu; Xue Bei; Chuanwei Zheng; Hong Lou; Huimei Tian; Wenjing Han; Wenxiao Sun; Songyan Jiao; Shuo Li; Bing Li; Lusheng Zhu; Zhongkun Du; et al. (Applied Soil Ecology, 2026)

Uniform phosphorus, divergent gains: Chicken and pig manures drive microbial metabolic functional diversity and nutrient synergy in reclaimed mining soil - Xin Chen; Hanqian Wu; Wuyan Du; Wenju Guo; Jie Zhang; Huisheng Meng; Yulin Liu; Jianping Hong; Minggang Xu; Xiangying Wang; Yi Li; Xianjun Hao (Plant and Soil, 2026)

Future Directions of Seaweed-based Bioeffectors and Biofertilizer - Muhamad Syaifudin; Jialong Xu; Wenkang Fan; Mohamed G. Moussa; Chenhui Zhong; Tangcheng Li; Hong Du (Journal of Soil Science and Plant Nutrition, 2026)

Regulation of vegetative propagation by exogenous α-NAA and GA1 in Sargassum hemiphyllum var. chinense - Yuming Wu; Qiong Wu; Yi Luo; Muhamad Syaifudin; Xianming Tang; Tangcheng Li; Jing Chen; Hong Du (Algal Research, 2026)

Corrigendum to ‘Phlecarinatones H–O: Abietane-type diterpenoids from Phlegmariurus carinatus with proliferative inhibitory effect on glioma’ [Phytochemistry 232 (2025) 114356/PHYTO_114356] - Hua Wang; Qiang Wang; Yong-Hong Chen; Xi Chen; Dong-Kun Zheng; Zhen Xie; Du-Min Feng; Lin Liu; Jing Li; Yang Liu (Phytochemistry, 2026)

Effects of earthworms on soil virus-associated ARGs and resistance phenotypes in long-term field cropping systems - Ying Ding; Bo-Wen Liu; Di Wu; Hong-Zhe Li; Shuai Du; Dong Zhu (Journal of Hazardous Materials, 2026)

Benzo[c]chromene-based light-emitting conjugated polymer for high performance deep-blue PLEDs - Hong Ren; Zhiyang Sun; Xiang An; Qian Wu; Xinyu Du; Xiaoqi Guo; Wenyu Chen; Mengyuan Li; Jiabin Liu; Dunliang He; Ning Sun; Lubing Bai; et al. (Chemical Engineering Journal, 2026)

Influence of structural changes of starch in starchy foods during storage on their edible quality: A review - Huan Xie; Yan Hong; Lingjin Li; Li Cheng; Jing Du; Zhaofeng Li; Caiming Li; Xiaofeng Ban; Zhengbiao Gu (Carbohydrate Polymers, 2026)

Intelligent Control System for Particulate Matter: Real-Time Monitoring and Pollution Source Identification for Enhanced Efficiency - Peng Shi-Tao; Li Long-Chuang; Ye Yin; Hong Ning-ning; Zhang Jing; Chen Zi Jing; Du Hong-Bo (Water, Air, & Soil Pollution, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

The role and therapeutic potential of purinergic signaling pathway in metabolic syndrome-related atherosclerosis - Xiang Li; Chengxin Gong; Chengxiao Fu; Qing Xia; Yue Zhang; Yue Du; Yuting Sun; Hong Xu (Purinergic Signalling, 2026)

Immunotherapy checkpoint inhibitor-combination therapy versus chemotherapy alone among Chinese population in cholangiocarcinoma treatment: a systematic review and meta-analysis - Li Shi; Wei Du; Juan Miao; Xi-Yuan Peng; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Si-Qi Gao; Hong-Lin Chen (European Journal of Clinical Pharmacology, 2026)

Source identification and risk assessment of PAC contamination in typical coal mining soils of Huaibei, China: application of PMF and APCS-MLR receptor models - Zheng Du; Guiyu Wu; Xiuping Hong; Kang Yang; Lichao Zhang; Yingying Zhang; Xin Wang; Kexin Li; Shuxian Wang; Ruonan Li; Zihan Wang (Environmental Geochemistry and Health, 2026)

Reproductive capacity and hereditary impact of triploid Crassostrea gigas and its aneuploid progeny - Xianchao Bai; Hong Hu; Chengxun Xu; Lingfeng Kong; Hong Yu; Shikai Liu; Haijun Liu; Shaojun Du; Qi Li (Marine Life Science & Technology, 2026)

Comprehensive evaluation and analysis of cold tolerance in Neopyropia yezoensis strains based on multiple traits - Zi-Xiang Zhai; Guo-Ying Du; Lan Wu; Lin Tian; Li-Hong Ma (Aquaculture, 2026)

Seismic response analysis of high-speed railway bridge systems spanning a V-shaped valley terrain on rigid bedrock - Pi-Guang Wang; Yi Chu; Hong-Jun Li; Mi Zhao; Xiu-Li Du (Soil Dynamics and Earthquake Engineering, 2026)

Cytochalasans from the fungus Chaetomium globosum with cytotoxic activities against HepG2 cell line - Hong-Fei Li; Tian Jin; Jiao-Xian Du; Xin-Wen Luo; Guo Zhang; Wang-Qiu Deng; Juan He; Tao Feng (Phytochemistry, 2026)

The combined effects of marine heatwaves and heavy metals on metal accumulation in macroalgae - Jiahui Chen; Muhamad Syaifudin; Tangcheng Li; Chenhui Zhong; Hong Du (Marine Environmental Research, 2026)

Interplay and integrated regulation of astaxanthin-lipid biosynthesis in microbial systems: A review from metabolic pathway cross-talk to biotechnological optimization - Zhipeng Li; Lifen He; Yuanzhen Song; Danling Tang; Fan Feng; Shaofan Cha; Tao Hong; Mingjing Zheng; Xiping Du; Yanbing Zhu; Yuanfan Yang; Zedong Jiang; et al. (Food Microbiology, 2026)

“Two-pronged” active packaging films enable biogenic amine scavenging and controlled Ferulic acid release for pork preservation - Hong Wang; Peng Shan; Jian Du; Chao Li; Yehan Tao; Jinwen Hu; Jie Lu; Chenglong Fu; Xiaodong Xia; Jijuan Cao; Haisong Wang (Chemical Engineering Journal, 2026)

Anti-Inflammatory Immunoregulatory Effects of Taurocholic Acid Are Mediated by TGR5 - Hong Su; Ziying Zhang; Chenguang Du; Hong Guan; Peifeng Li; Guifang Cao; Caiyun Wang (Bulletin of Experimental Biology and Medicine, 2026)

Hidden Role of Trophic Cascade Effects for Soil Carbon Sequestration in Alpine Tundra - Xinchang Kou; Ziwei Wang; Yan Tao; Yakov Kuzyakov; Shengzhong Wang; Ziping Liu; Haitao Wu; Hong S. He; Haibo Du; Mai‐He Li (Global Change Biology, 2026)
Large soil organic carbon (SOC) stocks in alpine tundra play a critical role in the global carbon budget but are increasingly vulnerable to loss under climate warming. These losses are partly driven by vegetation shifts, such as the upward migration of herbaceous plants, which alter soil food web structure and influence SOC sequestration. Although interactive effects between these processes are expected, they remain largely unclear or hidden. Here, we conducted a 13 C‐labeled glucose tracing experiment in the alpine tundra of Changbai Mountain to investigate how upward migration of Deyeuxia angustifolia affects soil food web structure, energy flows, and ultimately SOC sequestration. Compared with soils without migration (NM), heavily herb‐migrated (HM) soils showed intensified carbon fluxes within trophic cascade, increasing carbon transfer to higher trophic levels, including fungivores, omnivores‐predators, plant‐parasites, meso‐ and macrofauna. Predators in HM soils progressively increased 13 C assimilation over the 30‐day period, while microbivores showed a 5‐day lag behind microbial 13 C uptake. This predator‐driven energy dissipation was 2–14 times greater in HM than in NM soils and constituted an inefficient carbon sequestration pathway that limited the formation of stable carbon pools. As a result, SOC turnover in HM soils was more than 50% lower than in NM soils, indicating a shift toward less stable organic matter forms and reduced net carbon accumulation. Overall, our findings demonstrate that soil food webs play a pivotal role in both “belowground shaping” and “aboveground feedback” processes during herbaceous plant migration and that strengthened trophic cascade effects redirect carbon flow toward inefficient pathways, thereby constraining SOC sequestration in alpine tundra ecosystems.

Dynamic behaviors of fertilizer droplets impacting tea leaf surfaces - Bin Hu; Hong Li; Yue Jiang; Longfei Du (Computers and Electronics in Agriculture, 2025)

Satellite mapping of emperor penguin habitat dispersal under climate extremes - Hong Lin; Xiao Cheng; Jinyang Du; John S. Kimball; Ziyu Yan; Teng Li; Tongwen Li; Yibo Li; Zilong Chen (Remote Sensing of Environment, 2025)

Dynamic characteristics of a novel floating offshore photovoltaic system with flexible rope-net connection - De-Qing Zhang; Hong-Wei Tian; Zhi-Ming Yuan; Shuang-Rui Yu; Jun-Feng Du; Hua-Jun Li (Ocean Engineering, 2025)

Analysis of flavor metabolism characteristics of quinoa (Chenopodium quinoa Willd.) sprout plant beverage by GC-IMS combined with intelligent sensory technology - Jian Ma; Jingyi Du; Wentao Zhang; Hui Zhao; Yanhong Ma; Huiru Hong; Wuyang Huang; Jian Li (Food Research International, 2025)

Emerging adsorbent systems for sugar-derived contaminants removal: Sustainable strategies for sugar processing wastewater remediation - Yan-Shu Xiong; Lu-Nan Zhao; Shu-Ya Du; Xian-Yan Tao; Yan-Hong Wei; Hai-Qin Lu; Wen Li; Kai Li; Hao Dong (Food Chemistry, 2025)

Individual and collaborative solid-state fermentation by Monascus purpureus and Eurotium cristatum: Impact on metabolite profiling and hypolipidemic properties of black Tartary buckwheat - Jiuhong Du; Li Xiong; Xiaoqing Chen; Yangyu Zhou; Wenyue Yu; Yue Xiao; Yuqin Yao; Yina Huang; Hong Gao (Food Chemistry, 2025)

Influence of simulated future climate CO2 scenarios on carbon allocation in a keystone cyanobacterium Synechococcus - Yanyan Zhang; Lincheng Huang; Yongxin Liu; Tangcheng Li; Hong Du; Faming Wang; Zhe Lu (Journal of Applied Phycology, 2025)

Radiotherapy promotes M2 polarization of macrophages through the regulation of the PTEN/PI3K/AKT signaling pathway through miR-616-3p in lung cancer cell-derived exosomes - Lei Yang; Zhixian Zhang; Yi Zhang; Lijuan Wang; Shuangzhi Zheng; Yongli Li; Decai Du; Changli Yuan; Hongxun Li; Zhi Zeng; Hong Liu; Juntao Yang (In Vitro Cellular & Developmental Biology - Animal, 2025)

Analyzing the potential targets and mechanism of per- and polyfluoroalkyl substances (PFAS) on breast cancer by integrating network toxicology, single-cell sequencing, spatial transcriptomics, and molecular simulation - Jiajun Li; Deqi Wang; Sihan Song; Yi Wang; Xinlei Wu; Zhuoyi Du; Yanggang Hong (Functional & Integrative Genomics, 2025)

Emergence of cfr(C) variant in Campylobacter coli derived food-producing animal origin - Hao Li; Yong Liu; Shuaiwei Ge; Hexiang Huang; Wenjun Li; Shihong Li; Xiaonan Li; Chenglong Li; Xiang-Dang Du; Chunyan Xu; Hong Yao (Veterinary Microbiology, 2025)

Characterization of lincomycin resistance gene lnu(C)-carrying Campylobacter jejuni - Wenjun Li; Shuaiwei Ge; Yong Liu; Hao Li; Hexiang Huang; Chunyan Xu; Chenglong Li; Xiang-Dang Du; Yanhong Shang; Hong Yao (Veterinary Microbiology, 2025)

Sorafenib induces intestinal toxicity by disturbing gut microbiota and activating the LPS/TLR4/NF-κB signaling pathway in mice - Yaning Xu; Yongshi Mo; Wenxin Zhou; Meirong Qin; Meifang Li; Guo Yin; Hansheng Yu; Yuchun Chen; Haiyan Du; Yibao Jin; Houshuang Huang; Chong Ma; et al. (Toxicology, 2025)

Seismic performance of utility tunnel and internal pipeline system based on fuzzy probability analysis - Jinqiang Li; Hong Hao; Zilan Zhong; Yuebo Shi; Xiuli Du (Soil Dynamics and Earthquake Engineering, 2025)

Biocontrol potential and antifungal mechanism of a novel Bacillus velezensis NH-13–5 against Botrytis cinerea causing postharvest gray mold in table grapes - Lin Xiao; Jin-Tian Wang; Dong-Fang Cao; Hong Li; Hong-Yu Fang; Tian-Li Qu; Bao-Hua Zhang; Shuai-Shuai Li; Feng-Yu Du (Postharvest Biology and Technology, 2025)

Molecular molybdenum catalyst covalently anchored onto a polystyrene resin for the alkylation of alcohols with ketones - Tao Wang; Di Wu; Fei Chen; Zhi-Hong Du; Chun-Bo Bo; Min Li; Ning Liu (Fuel, 2025)

EPA-enriched phospholipids and DHA-enriched phospholipids prevent dexamethasone-induced skeletal muscle atrophy via regulating protein turnover and mitochondrial quality - Ying-Chao Li; Shi-Xiang Wu; Qing-Yan Zou; Yan Zheng; Zi-Jian Wu; Xin-Yue Zhao; Xiang Gao; Yu-Hong Yang; Lei Du (Food Research International, 2025)

Establishment of succinic acid production in recombinant Kluyveromyces marxianus enhanced by AI-guided enzyme specificity engineering and redox-controlled fermentation optimization - Du-Wen Zeng; Yi-Fan Zhu; Yuan-Hong Jiang; Ya-Hao Ding; Zhen-Zhi Wang; Kai Li; Sha Liao; Ya-Chao Fan; Lin Zhang; Yu Guang Wang; Xin-Qing Zhao (Chemical Engineering Journal, 2025)

Assessment of environmental and health impacts during 3D printing of candidate polymeric materials for space additive manufacturing - Junling Li; Yi Liu; Chao Peng; Qifan Liu; Wei Zhao; Mingyuan Liu; Xinyu Du; Yongyin Yan; Yufei Song; Kaihui Xia; Chun Chen; Haijie Zhang; et al. (Journal of Hazardous Materials, 2025)

Thermodynamic mechanism of metallurgical-grade silicon preparation from silica fume by carbothermal reduction - Hongbing Du; Yao Chen; Yaoxuan Wang; Hong Wang; Xiaolin Guo; Zhaoyang Zhang; Haiyu Li; Pengfei Xing; Yanxin Zhuang (Journal of Cleaner Production, 2025)

Metal-organic framework ZIF-67 derived Co@CN catalysts for the promising generation of hydrogen from ammonia decomposition - Tianxiang Li; Xiaofeng Gu; Qing Wang; Kailong Zhang; Wanze Li; Hong Du; Hewen Liu; Emin Aili; Yufang Ye; Xiao Chen (Fuel, 2025)

Curcumin-mediated photodynamic treatment efficiently inhibits Bacillus cereus and extends the shelf-life of flat rice noodles - Hao-Ran Ji; Jia-Jun Yan; Zi-Hui Chen; Wen-Li Shi; Li-Wen Chen; Juan Wang; Yu Ding; Ai-Min Jiang; Bing Du; Cai-Hu Liao; Hong-Tao Lei; Quan Zhou; et al. (Food Research International, 2025)

Collaborative passivation of defects and enhancing crystallization enabled by an additive with multiple active sites for inverted perovskite solar cells - Qing Du; Shangwei Feng; Yue Liang; Bufan Yu; Jiacheng Liu; Yihang Li; Wei Hong; Lei Wang; Guichuan Xing; Jiangshan Chen; Dongge Ma (Chemical Engineering Journal, 2025)

Flame retardant modified starch adhesive made by crosslinking with phosphorus containing citrate based polyamines has excellent boiling water resistance - Hong Cao; Zhenqiang Kan; Wenxuan Feng; Yuju Chen; Jinzhong Yao; Dongyu Wei; Yuefeng Huang; Lianpeng Zhang; Guanben Du; Li Liu (Carbohydrate Polymers, 2025)

HFIP-driven Schmidt-type reaction enables chromone-3-carbonitriles and its applications - Jia Xu; Jie Lei; Li-Xin Zhang; Shan Yu; Cheng-He Zhou; Zhi-Gang Xu; Hong-Wei Du; Zhong-Zhu Chen (Molecular Diversity, 2025)

Effects of AMPEP (Ascophyllum marine plant extract powder) and SJEP (enzymatic extracts of Saccharina japonica) on growth and resistance of red macroalga Pyropia yezoensis - Guo-Ying Du; Li-Hong Ma; Yu-Qing Wang; Xin-Yu Zhang; Yan-Jun Gong; Dong-Mei Wang (Algae, 2025)
Seaweed extracts are widely used as biostimulants in terrestrial crops but remain underexplored for economic macroalgae. This study investigated the effects of Ascophyllum marine plant extract powder (AMPEP) and Saccharina japonica extract powder (SJEP) on the growth and stress resistance of Pyropia yezoensis, a commercially significant red macroalga along the Northeast Asia coast. Through gradient analysis, optimal concentrations were determined to be 0.05 g L−1 for SJEP and 0.1 g L−1 for AMPEP, based on their effects on daily growth rate (DGR) and photosynthetic performance. Both extracts significantly improved resistance to red rot disease, reducing lesion area while increasing DGR, photosynthetic efficiency, and pigment content compared to the control. Additionally, SJEP and AMPEP elevated superoxide dismutase (SOD) activity and suppressed malondialdehyde (MDA) accumulation. Under cold stress, the extracts mitigated declines in DGR, photosynthetic parameters, pigment levels, and SOD activity, while restraining MDA elevation. Notably, the expression of cold-responsive genes (PyABCC1 and PyABCI1) peaked in SJEP treatment and remained elevated in AMPEP treatment, surpassing the control by several-fold. Overall, SJEP outperformed AMPEP, likely due to its higher polysaccharide and polyphenols. These results support brown algal extracts—particularly enzymatic extracts—as practical biostimulants to enhance growth, disease resistance, and cold tolerance in P. yezoensis cultivation.

The application of integrated deep learning models with the Assistance of meteorological factors in forecasting major tobacco diseases - Yuan Chen; Changcheng Li; Can Wang; Yansong Xiao; Tianbo Liu; Jiaying Li; Kai Teng; Hailin Cai; Zhipeng Xiao; Hong Zhou; Xiangping Zhou; Weiai Zeng; et al. (Computers and Electronics in Agriculture, 2025)

Role of biochar in reducing polyethylene and polylactic acid microplastic co-contamination with antibiotics in soil-vegetable systems - Pengfei Cheng; Junliang Chen; Muhammad Tariq; Lei Tang; Zebin Hong; Babar Iqbal; Ismail Khan; Guanlin Li; Daolin Du; Tongxu Liu (Process Safety and Environmental Protection, 2025)

Petrological and thermodynamic constraints on carbonate stability in altered oceanic crust subducted to subarc depths: Insights from carbonate-bearing eclogites in the Western Alps - Zeng-Li Guo; Jin-Xue Du; Li-Fei Zhang; Thomas Bader; Ren-Biao Tao; Ze-Ming Zhang; Kurt Bucher; Ting-Nan Gong; Jin-Hong Yu (Geochimica et Cosmochimica Acta, 2025)

Diaporthein B/ZnO/chitosan biodegradable film for postharvest preservation of apples: Characterization and application - Hui-Fang Du; Fei Cao; Zhi-Hong Xu; Ya-Xian Gao; Ya-Hui Zhang; Sen Pang; Wan Li; Long-Fei Li; Li Han; Li-Juan Wang; Hong-De An (Food Packaging and Shelf Life, 2025)

Distribution and partitioning behavior of phthalate esters (PAEs) and non-phthalate ester plasticizers (NPPs) in a home from northern China - Chun-Yan Huo; Li-Yan Liu; Liang Wang; Yu Sun; Shuang Du; Li Song; Yong-Yu Li; Xin-Hong Wang; Wen-Long Li (Environmental Pollution, 2025)

Interface enhanced catalytic hydrodeoxygenation of vanillin as a bio-oil model using Ni-based catalysts - Kuan Du; Hong Li; Long Jiang; Kai Xu; Jun Xu; Yi Wang; Sheng Su; Song Hu; Jun Xiang (Chemical Engineering Journal, 2025)

Simulation-guided plasma surface engineering for enhanced triboelectric Nanogenerator performance - Hong Yu; Haonan Ma; Zuying Huang; Mengya Lin; Junming Chen; Ruibin Wu; Ye Tao; Chengrun Li; Ruijia Yang; Xiaozhen Du (Chemical Engineering Journal, 2025)

High efficiency phenol removal from wastewater with low energy consumption enabled by an electropolymerization membrane reactor - Hong Wang; Xiaolong Ge; Minghui Du; Jiawei Dong; Qingqing Wang; Binzhi Zhang; Peiyong Wang; Jianxin Li (Chemical Engineering Journal, 2025)

County-level coordination between urbanization and ecological change in dryland urban agglomerations: A quantitative approach based on remote sensing - Chunqiang Li; Shanchuan Guo; Zilong Xia; Xiaoquan Pan; Haowei Mu; Hong Fang; Pengfei Tang; Peijun Du (Journal of Geographical Sciences, 2025)

A new combined model for forecasting geomagnetic variation - Chao Niu; Yi-wei Wei; Xi-hai Li; Hong-ru Li; Xiao-niu Zeng; Ji-hao Liu; Ai-min Du (Applied Geophysics, 2025)

Cumulative effects of ocean currents and land-based pollution on the abundance and composition of coastal zooplankton - Liang-gen Wang; Peng-bing Pei; Muhammad Aslam; Tang-cheng Li; Xiao Ke; Xiu-li Yan; Fei-yan Du; Hong Du (Marine Environmental Research, 2025)

A novel phase optimization method to improve microwave heating uniformity - Yuanyuan Li; Yao Zhang; Yuhong Du; Tao Hong; Dezhi Gou; Lin Wang; Zhengming Tang (Journal of Food Engineering, 2025)

Strong heterogeneity in laterally exchanged particulate organic matter across tidal marshes in a large river delta - Qi Wu; Hong-Sheng Cao; Youhei Yamashita; Christian Lønborg; Run Li; Jianzhong Ge; Hualei Yang; Bolin Liu; Jinzhou Du; Fang Cao (Environmental Research, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Study on sand column collapse mechanisms through optical frequency domain reflectometry and particle image velocimetry - Dao-Yuan Tan; Ning Ma; Yong-Qin Li; Hong-Hu Zhu; Lei Gao; Du-Min Yan; Wan-Huan Zhou (Bulletin of Engineering Geology and the Environment, 2025)

Remarkable metabolic reconfiguration due to three classical nitrogen sources in Gracilariopsis lemaneiformis (Rhodophyta) - Wenkang Fan; Chunyou Yang; Dingzhi Song; Peilin Ye; Honghao Liang; Chunping Huang; Muhamad Syaifudin; Chenhui Zhong; Tangcheng Li; Hong Du (Algal Research, 2025)

A nanofiltration and electrocatalytic membrane reactor with ozone oxidation integrated system for dyeing wastewater treatment and Na2SO4 recovery - Minghui Du; Ruohan Wang; Hong Wang; Jianxin Li (Water Research, 2025)

Deciphering heavy metal adsorption capacity of soil based on its physicochemical properties and adsorption reaction time using machine learning - Jianle Wang; Xueming Liu; Weijie Li; Yuliang Tu; Hong Deng; Jianwei Du (Journal of Environmental Chemical Engineering, 2025)

Altering wilting time and chopping length to optimize Medicago polymorpha L. fermentation ripening rate and flavour - Ning Mao; Hanyu Zhang; Ermei Du; Meiling Fan; Shihao Liu; Chaosheng Liao; Chao Chen; Hong Sun; Yulong Zheng; Ping Li; Yixiao Xie (Food Bioscience, 2025)

Enhancing the quality of dark tea through fermentation with Aspergillus niger: Unveiling aroma and taste characteristics - Maoyun Li; Sicheng Du; Yue Xiao; Yanping Wu; Kai Zhong; Yina Huang; Renyou Gan; Hong Gao (Food Microbiology, 2025)

Adipose-derived EVs loaded resolvins biopotentiated decellularized extracellular matrix hydrogels accelerate muscle regeneration - Qizhi Shuai; Jingwen Cheng; Xiaowan Wang; Xueling Li; Ke Xu; Min Ge; Zulala Halbiyat; Zehang Wang; Genlai Du; Tingjuan Huang; Zhiwei Peng; Hong Zhao; et al. (Chemical Engineering Journal, 2025)

Mesenchymal stem cell exosomes regulate TGFβ/Smad3 by decreasing the METTL3-NEAT1 axis to inhibit scar progression after breast surgery - Juan Du; Jincheng Wu; Qinqin Song; Shuangru Li; Youwang Hong; Aizaz Anwar; Quanyou Fu; Jisong Liu (Journal of Molecular Histology, 2025)

The impact of salinity on heavy metal accumulation in seaweed - Muhamad Syaifudin; Mohamed G. Moussa; Tangcheng Li; Hong Du (Marine Pollution Bulletin, 2025)

Characterization of cross-resistance gene optrA-carrying Campylobacter coli - Jin Kang; Shuigen Wan; Wenbo Zhao; Shihong Li; Wenjun Li; Hao Li; Yong Liu; Hexiang Huang; Chunyan Xu; Xiang-Dang Du; Hong Yao (Veterinary Microbiology, 2025)

Pronounced advance on typhoon track forecast with global convection-permitting model - Jun Gu; Chun Zhao; Gudongze Li; Jiawang Feng; Mingyue Xu; Qiuyan Du; Zihan Xia; Yubin Li; Guanghua Chen; Xiaoyu Hao; Junshi Chen; Hong An (Science Bulletin, 2025)

Research of lean burn characteristics and interaction of hydrogen direct injection engine based on response surface methodology - Zhendong Liang; Fangxi Xie; Jiakun Du; Hong Chen; Xiaoping Li; Kaichang Lai (Fuel, 2025)

Crystal facet effect of the support in Ni/La2O2CO3 catalysts for toluene steam reforming - Shou-Yong Jiang; Yang Du; Yun-Jie Li; Zhi-Bin Wang; Hong-Xia Fan; Shou-Dong Xu; Zhen-Yi Du; M.D. Isobaev; Wen-Ying Li (Fuel, 2025)

Antioxidant and antimicrobial PSE-like chicken protein isolate films loaded with oregano essential oil nanoemulsion for pork preservation - Chen-Yan Zhu; Ke Li; Yu Wang; Man-Ting Du; Bo Chen; Yun-Tao Wang; Yan-Fang Zhou; Yan-Hong Bai (Food Chemistry, 2025)

Physiological and molecular responses to urea environment in Cladocopium goreaui (Symbiodiniaceae) - Cristiana Manullang; Jiahong Huang; Wei Lin; Honghao Liang; Hong Du; Tangcheng Li (Environmental Research, 2025)

Iron isotopic fractionation during seafloor hydrothermal alteration of oceanic upper crust, as recorded in Geotimes lavas of Semail ophiolite, Oman - Rong-Zhong Bo; Yildirim Dilek; Wei-Qiang Li; Sobhi Nasir; Peng-Jie Cai; Hui-Chao Rui; De-Hong Du; Shi-Chao An; Yu-Xiao Lu; Hao-Chen Duan; Dong-Yang Lian; Jing-Sui Yang; et al. (Chemical Geology, 2025)

FNDC5 alleviates Ox-LDL-induced HUVECs dysfunction by inhibiting ferroptosis through AMPK/Nrf2 signaling - Yipeng Du; Hong Ouyang; Huiyong Wang; Jian Shi; Yuanqing Li; Lingling Xu; Caiyun He; Xiudi Pan; Huidong Long (Tissue and Cell, 2025)

Phlecarinatones H–N: Abietane-type diterpenoids from Phlegmariurus carinatus with proliferative inhibitory effect on U251 glioblastoma cells - Hua Wang; Qiang Wang; Yong-Hong Chen; Xi Chen; Dong-Kun Zheng; Zhen Xie; Du-Min Feng; Lin Liu; Jing Li; Yang Liu (Phytochemistry, 2025)

Dysregulation of Iron Homeostasis Mediated by FTH Increases Ferroptosis Sensitivity in TP53-Mutant Glioblastoma - Xuejie Huan; Jiangang Li; Zhaobin Chu; Hongliang Zhang; Lei Cheng; Peng Lun; Xixun Du; Xi Chen; Qian Jiao; Hong Jiang (Neuroscience Bulletin, 2025)

DOPA Decarboxylase (DDC) in Pacific Oysters: Characterization and Role in Tyrosine Metabolism and Melanogenesis - Kunyin Jiang; Hong Yu; Lingfeng Kong; Shikai Liu; Shaojun Du; Qi Li (Marine Biotechnology, 2025)

Co-occurrence of mcr-9 and blaNDM-5 in Multidrug-Resistant Enterobacter hormaechei Strain Isolated from a Patient with Bloodstream Infection - Ru Li; Junfeng Wang; Weiting Zhang; Chenhao Zhao; Mingxiao Han; Hong Du; Haifang Zhang (Current Microbiology, 2025)

Correction: Inhibition of 12/15 lipoxygenase by baicalein reduces myocardial ischemia/reperfusion injury via modulation of multiple signaling pathways - Lina Song; Hui Yang; Hong-Xia Wang; Cui Tian; Yu Liu; Xiang-Jun Zeng; Erhe Gao; Yu-Ming Kang; Jie Du; Hui-Hua Li (Apoptosis, 2025)

Urea Amidolyase as an Enzyme for Urea Utilisation in Phytoplankton: Functional Display in Chlamydomonas reinhardtii - Honghao Liang; Tangcheng Li; Yuanhao Chen; Jingtian Wang; Muhammad Aslam; Huaizhi Qin; Wenkang Fan; Hong Du; Shuh‐ji Kao; Senjie Lin (Molecular Ecology, 2025)
Urea is an important source of nitrogen for many phytoplankton with the potential to stimulate harmful algal blooms, but the molecular machinery underpinning urea uptake and assimilation by algae is not fully understood. Urease (URE) is commonly regarded as the responsible enzyme, but urea amidolyase (UAL), albeit known to exist, has hardly been studied. Here, the species distribution, expression patterns and functional roles of UAL are examined. We found a widespread occurrence of UAL across six major phytoplankton lineages, along with evidence of a potential URE‐independent evolutionary trajectory and lineage‐specific losses. Quantitative analyses based on marine planktonic metagenomes and metatranscriptomes revealed that UAL is as prevalent as URE, but exhibits higher expression levels in phytoplankton than in bacteria, suggesting that UAL plays a crucial role in nitrogen nutrition in marine phytoplankton. Furthermore, using the CRISPR/Cas9 genome editing method and Chlamydomonas reinhardtii as the algal model, we showed that DUR2 in UAL is essential for urea utilisation, as its knockout completely abolishes the ability of algae to grow under urea as the sole nitrogen source. This study unveils an unappreciated mechanism in algae for utilising urea as a nutrient, underscores the need to consider both URE and UAL enzyme systems to model urea utilisation by algae and provides a crucial gene ( DUR2 ) as a potential genetic marker for detecting the contribution of UAL to urea utilisation in phytoplankton.

Aflatoxin B1 exposure induces Alzheimer's disease like pathology by disrupting redox homeostasis and activating ferroptotic signals in C57BL/6 J mice - Jinxian Lin; Huihui Hong; Sicheng Liu; Zhengwei Liang; Qixue Zheng; Kun Luo; Jiayi Li; Zhulin Du; Jinping Yu; Lingling Yang; Ping Deng; Huifeng Pi; et al. (Science of The Total Environment, 2025)

Chronic sublethal exposure to chlorantraniliprole inhibits growth and development by disrupting the sugar and fatty acid metabolism in Spodoptera frugiperda - Xiao-Guang Liu; Qing-Ge Wang; Xiao-Ming Liu; Xiang Li; Meng-Fang Du; Cai-Hong Tian; Yun-Hui Zhang; Shi-Heng An (Pesticide Biochemistry and Physiology, 2025)

Mechanism of anti-hepatitis potential of Tagetes erecta L.: UPLC-Q-TOF-M S/MS, network pharmacology, molecular docking and in vitro experimental validation - Jiangning Peng; Zhenxia Zhao; Zhiqian Yuan; Yingfeng Du; Hong Wang; Yunhe Lian; Xinyi Yang; Hui Li (Next Research, 2025)

Late Quaternary vertical throw rates along the Gyaring Co fault in central Tibet - Duo Wang; Lichun Chen; Hong Chang; Shugang Kang; Yongshun Jia; Jinhua Du; Fei Han; Yanbao Li; Gongming Yin; Wenjun Zheng; Xulong Wang (Journal of Asian Earth Sciences, 2025)

Visible-Light-Driven (NSNO)Nickel complex catalyzed (Z)-Selective semi-hydrogenation of alkynes - Nuo Zhang; Yong-Bo Zhou; Fei Chen; Zhi-Hong Du; Chun-Bo Bo; Min Li; Ning Liu (Fuel, 2025)

The Effect of Urbanization and Farmland to Forests Program on Surface Runoff - Jing Zhang; Zi-Jing Chen; Yong Ma; Qing Xie; Wen-jie Li; Hong-bo Du (Water Resources Management, 2025)

Advances in regional-scale crop growth and associated process modeling - Wenfeng Liu; Yawei Bai; Taisheng Du; Mengxue Li; Hong Yang; Shichao Chen; Chuanbin Liang; Shaozhong Kang (Science China Earth Sciences, 2025)

Correction to: Autophagy in Oligodendrocyte Lineage Cells Controls Oligodendrocyte Numbers and Myelin Integrity in an Age-dependent Manner - Hong Chen; Gang Yang; De-En Xu; Yu-tong Du; Chao Zhu; Hua Hu; Li Luo; Lei Feng; Wenhui Huang; Yan-Yun Sun; Quan-Hong Ma (Neuroscience Bulletin, 2025)

Autophagy in Oligodendrocyte Lineage Cells Controls Oligodendrocyte Numbers and Myelin Integrity in an Age-dependent Manner - Hong Chen; Gang Yang; De-En Xu; Yu-tong Du; Chao Zhu; Hua Hu; Li Luo; Lei Feng; Wenhui Huang; Yan-Yun Sun; Quan-Hong Ma (Neuroscience Bulletin, 2025)

Synthesis, Structure and Luminescence Properties of Novel Red-Emitting Na2SrSi2O6:Eu3+ Phosphors - Yunxiang Du; Yingchao Xu; Subin Wang; Junhuang Hong; Jing Li; Yuxuan Wei; Zhifang Liu (Journal of Fluorescence, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Pacific Walker Circulation modulated millennial-scale East Asian summer monsoon rainfall variability over the past 40 kyr - Yi Zhong; Yuxing Liu; Xiaojing Du; Xiaoxu Shi; Xing Xu; Zhengyao Lu; Stefanie Kaboth-Bahr; Mark J. Dekkers; Juan C. Larrasoaña; Keiji Horikawa; Chijun Sun; Liang Ning; et al. (Global and Planetary Change, 2025)

Synergistic effect of 2′-Fucosyllactose or galactooligosaccharide with Bifidobacterium bifidum DNG6 improves the intestinal barrier by modulating the SCFAs-TLR4/NF-κB cascade response in DSS-induced colitis in mice - Cui-Cui Sun; Yu-Qi Wang; Xin-Yu Wang; Guo-Fang Zhang; Hong-Fang Cao; Ge Song; Li-Bo Liu; Chun Li; Irina Valeryevna Boyarineva; Peng Du (Food Bioscience, 2025)

A carbon membrane-aerated electrochemical reactor for efficient electrosynthesis of H2O2 - Jiawei Dong; Minghui Du; Hong Wang; Zhengyu Cui; Shuanglin Gui; Qinliang Jiang; Jianxin Li (Chemical Engineering Journal, 2025)

CgPPOX and CgFECH Mediate Protoporphyrin IX Accumulation Predominantly in the Outer Mantle Fold of Pacific Oyster Crassostrea gigas - Biyang Hu; Hong Yu; Lingfeng Kong; Shikai Liu; Shaojun Du; Qi Li (Marine Biotechnology, 2025)

Examination of the roles of CgTH in tyrosine metabolism and pigmentation of Pacific oyster (Crassostrea gigas) - Kunyin Jiang; Hong Yu; Lingfeng Kong; Shikai Liu; Shaojun Du; Qi Li (Aquaculture, 2025)

Assessment of forest disturbance and soil erosion in wind farm project using satellite observations - Zilong Xia; Yingjie Li; Shanchuan Guo; Xingang Zhang; Xiaoquan Pan; Hong Fang; Ruishan Chen; Peijun Du (Resources, Conservation and Recycling, 2025)

Effects of degree of milling on bran layer structure, physicochemical properties and cooking quality of brown rice - Juan Li; Shuai Yang; Zhiming Zhong; Tianli Xia; Wenju Zhou; Zhaoxin Tu; Zhengxing Chen; Hong Wang; Zhihua Dai; Gangqiang Jin; Yan Du (Food Chemistry, 2025)

Numerical investigation on plastic hinge behavior of hybrid steel-FRP reinforced concrete columns - Ping Li; Liu Jin; Wensu Chen; Hong Hao; Xiuli Du (Engineering Structures, 2025)

CoOx confined in layered montmorillonite serving as PMS activator for wastewater treatment - Piao Xu; Hong Qin; Quyang Tian; Ziwei Wang; Yangzhuo He; Fuqi Wu; Li Du; Guangfu Wang; Wenyang Li; Ying Zeng; Han Wang (Chemical Engineering Journal, 2025)

Antifungal mechanism and application to phytopathogenic fungi after anaerobic fermentation of Gracilaria agar wastewater - Boyan Duan; Yanyan Wu; Shanyu Xie; Tao Hong; Yuanfan Yang; Mingjing Zheng; Zedong Jiang; Yanbing Zhu; Qingbiao Li; Hui Ni; Yuanpeng Wang; Xiping Du; et al. (Bioresource Technology, 2025)

Time and environmental conditions for heat stress recovery based on human physiological responses: Developing a predictive model - Liangyue Shang; Baizhan Li; Shan Zhou; Chenqiu Du; Runming Yao; Yanfeng Zhu; Guangyi Chen; Peiping Zheng; Hong Liu (Building and Environment, 2025)

A green strategy to realize the high value utilization of lignin for hydrogel formation - Tingjun Song; Hong He; Xinling Li; Xueqian Liu; Yanna Lv; Yehan Tao; Jie Lu; Jian Du; Jinwen Hu; Haisong Wang (Science of The Total Environment, 2024)

Mechanisms of selectivity for azadirachtin in honeybees (Apis cerana): A new strategy for avoiding thiamethoxam ingestion - Hao Wu; Sheng-nan Li; Rui-quan Hou; Peng-rui Du; Kun-yu Zhao; Muhammad Zeeshan; Han-hong Xu; Zhi-xiang Zhang; Pei-wen Zhang (Pesticide Biochemistry and Physiology, 2024)

Magmatic differentiation of peralkaline granites: Constraints from iron isotope fractionation between Fe-bearing minerals - De-Hong Du; Xiao-Lei Wang; Hang Xu; Shuo Wang; Ying-Ze Zhang; Weiqiang Li (Lithos, 2024)

The correlation between single and mixed trace elements exposure in systemic lupus erythematosus: A case-control study - Rong-Gui Huang; Kai-Di Li; Hong Wu; Yi-Yu Wang; Ya Xu; Xue Jin; Yu-Jie Du; Yi-Yuan Wang; Jing Wang; Zhang-Wei Lu; Bao-Zhu Li (Journal of Trace Elements in Medicine and Biology, 2024)

Cyanobacterial blooms prediction in China’s large hypereutrophic lakes based on MODIS observations and Bayesian theory - Yichen Du; Huan Zhao; Junsheng Li; Yunchang Mu; Ziyao Yin; Mengqiu Wang; Danfeng Hong; Fangfang Zhang; Shenglei Wang; Bing Zhang (Journal of Hazardous Materials, 2024)

Experimental study of NaHCO3/modified vermiculite composite powder for methane explosion suppression - Ke Yang; Lekai Li; Hong Ji; Dongyu Ji; Zhixiang Xing; Juncheng Jiang; Xiaoyang Du (Fuel, 2024)

Green, mild, and rapid plasma synthesis of nitrogen/amino-cofunctionalized MWCNTs-supported Pd catalyst in solution for boosting formic acid dehydrogenation - Xiaonan Du; Fei Gao; Yue Hua; Xiuling Zhang; Hong Li; Lanbo Di (Fuel, 2024)

Bioremediation of PAHs-contaminated site in a full-scale biopiling system with immobilized enzymes: Removal efficiency and microbial communities - Litao Wang; Guanyu Chen; Xuran Du; Meng Li; Zhou Zhang; Hong Liang; Dawen Gao (Environmental Research, 2024)

Records of Fukushima accident-derived cesium-137 in the Chukchi Sea sediment: Implication for a new time marker? - Xu Ren; Jinlong Wang; Gi Hoon Hong; Linwei Li; Qiangqiang Zhong; Dekun Huang; Tao Yu; Jinzhou Du (Science China Earth Sciences, 2024)

Genome-Wide Characterization of ABC Transporter Genes and Expression Profiles in Red Macroalga Pyropia yezoensis Expose to Low-Temperature - Lin Tian; Lan Wu; Xue-Feng Zhong; Li-Hong Ma; Guo-Ying Du (Marine Biotechnology, 2024)

Influence of urban functional zone change on land surface temperature using multi-source geospatial data: A case study in Nanjing City, China - Hong Fang; Shanchuan Guo; Chenghan Yang; Bo Yuan; Chunqiang Li; Xiaoquan Pan; Pengfei Tang; Peijun Du (Sustainable Cities and Society, 2024)

Morphological, molecular and pathogenic characterization of Botryosphaeria dothidea causing leaf blight disease of Polygonatum cyrtonema in China - Jinxin Li; Huixia Cai; Yanling Du; Hong Chen; Kaili Qu; Lu Wei; Yuhuan Miao; Dahui Liu (Physiological and Molecular Plant Pathology, 2024)

Mechanism study on the synergistic degradation of DMAC wastewater by electrocatalytic carbon membrane reactor coupled with persulfate dual catalysis - Hong Wang; Jing Han; Minghui Du; Zhaohui Yin; Qingqing Wang; Xiaolong Ge; Zhen Yin; Jianxin Li (Journal of Water Process Engineering, 2024)

Season-dependent climate sensitivity of the surface runoff of major rivers in Changbai Mountain - Xinran Li; Hong S. He; Na Li; Heyuan Yu; Shengwei Zong; Zhengfang Wu; Haibo Du (Journal of Hydrology, 2024)

Serum levels of per- and poly-fluoroalkyl substances among middle-aged and elderly populations in Beijing and their association with dyslipidemia - Lan Zhang; Jing Du; Qiaozhen Guo; Xin Xu; Hong Li; Nannan Zhong; Jing Zhang; Gang Li; Bing Shao (Food and Chemical Toxicology, 2024)

ZnO nanoparticles induce melanoma-like lesions via recruiting dermal dendritic cells in barrier-damaged skin in mice - Menghan You; Yingying Huang; Yeda Chen; Dan Li; Yaping Tang; Yi kuan Du; Hong Yang; Anfa Liang; Guodong Hu; Yinghua Chen (Food and Chemical Toxicology, 2024)

Seismic behavior and resilience assessment of prefabricated beam–column joint with replaceable graded-yielding energy-dissipating connectors - Yongfeng Du; Fangyu Li; Hu Li; Na Hong; Peihong Chi (Engineering Structures, 2024)

An Eco-friendly β-cyclodextrin/Stilbene-Integrated supramolecular material Realizes the effective treatment of bacterial diseases via enhancing the biofilm eradication and Agrochemical bioavailability - Li Zhou; Yazhen Chen; Jinghan Yang; Yaling Duan; Huiqin Gong; Haojie Ye; Ya Hong; Min Liu; Gefei Hao; Fengpei Du; Peiyi Wang (Chemical Engineering Journal, 2024)

Acid-Resistant bioorthogonal quantum nanoprobes for noninvasive NIR-II imaging of simulated microgravity-induced gastric bacterial alterations in rats - Yiyang Du; Mengyao Su; Weicheng Yang; Zhujun Wu; Yuankun Zhao; Tingjun Yan; Naiqing Li; Yudi Pang; Yingying Li; Hong Ma; Zhimin Wang; Yulin Deng; et al. (Chemical Engineering Journal, 2024)

A preliminary study of T-2 toxin that cause liver injury in rats via the NF-kB and NLRP3-mediated pyroptosis pathway - Shicong Zheng; Haonan Li; Hexuan Dong; Fang Qi; Bing Zhang; Qian Yu; Buyi Lin; Hong Jiang; Haoyu Du; Ying Liu; Jun Yu (Toxicon, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Novel Cu(I)/Cu(II) oxide nanowires electrode with efficient cyclic catalytic performance for electroreduction of nitrate wastewater to ammonia - Ye Du; Wenjie Liu; Changhui Zhou; Chaoyue Xie; Zhinan Dai; Jie Wang; Jia Lin; Jinhua Li; Hong Zhu; Jing Bai; Baoxue Zhou (Journal of Environmental Chemical Engineering, 2024)

Estimating river discharge across scales with a novel regional gauging method driven by Sentinel satellite data - Hong Lin; Xiao Cheng; Junguo Liu; Qian Shi; Teng Li; Lei Zheng; Xuejiao Hou; Jinyang Du (Remote Sensing of Environment, 2024)

Understanding the extreme differentiation of granitic magmas through elemental geochemistry and Fe isotope signatures - Xiang-Long Luo; Chang-Zhi Wu; Jia-Xin She; Matthew J. Brzozowski; De-Hong Du; Shichao An; Weiqiang Li (Geochimica et Cosmochimica Acta, 2024)

Analysis of flavor substances changes during fermentation of Chinese spicy cabbage based on GC-IMS and PCA - Wenkui Guo; Meiru Cheng; Xuemei Dong; Chuan Liu; Yu Miao; Peng Du; Hong Chu; Chun Li; Libo Liu (Food Research International, 2024)

Efficacy of a new K3-specific bacteriophage for controlling Klebsiella pneumoniae in milk and its potential to disrupt biofilm formation - Pei Li; Yu Zhou; Genglin Guo; Xiayan Qin; Zimeng Hu; Min Li; Zhongming Tan; Yuqing Liu; Xiangan Han; Jiale Ma; Hong Du; Wei Zhang (Food Control, 2024)

Simulated Yak and Tibetan Sheep Urine Deposition Fleetingly Promoted N2O, CO2 and CH4 Emissions in an Alpine Steppe of Northern Xizang Plateau - Jiaxiu Li; Xiaodan Wang; Jian Sun; Jiangtao Hong; Xiaoke Zhang; Ziyin Du; Jing Du; Zhaoyang Xiong; Xue Zhang; Ying Cao; Shuang Wang (Journal of Soil Science and Plant Nutrition, 2024)

Variation in Chongqing finger citron components and antioxidant activity from essential oils in several organs - Shang Fang-Hong; Chen Yu; Du Hong-Fei; He Jiang; Wu Zhen; Song Xu-Hong; Li Long-Yun (South African Journal of Botany, 2024)

Polygonatum kingianum Coll. et Hemsl enzymatic saccharifying extracts alleviate HFD-induced obesity in mice via regulating gut microbiota and AMPK pathways - Yanli Li; Junyuan Huang; Wenjun Zhao; Ziwen Guan; Ziyu Wang; Hong Huang; Rongxiang Guo; Lei Zhao; Pan Li; Bing Du (Food Bioscience, 2024)

Teleost-specific TLR23 in Takifugu rubripes recruits MyD88 to trigger ERK pathway and promotes antibacterial defense - Yu-ting Du; Hong-qiang Zhang; Yan Li; Xue-peng Li; Zeng-zhi Yuan; Mo-fei Li (Fish & Shellfish Immunology, 2024)

OysterDB: A Genome Database for Ostreidae - Xinchun Li; Yitian Bai; Chengxun Xu; Shikai Liu; Hong Yu; Lingfeng Kong; Shaojun Du; Qi Li (Marine Biotechnology, 2024)

Two new alkaloids from the endophytic fungus Schizophyllum sp. HM230 isolated from Vincetoxicum mongolicum Maxim - Zhuang Li; Bing-Wen Zhang; Li Jiang; He Wang; Qing-Yun Ma; Hong-Fei Wang; Jun Zhang; Feng-Li Chen; You-Xing Zhao; Du-Qiang Luo (Natural Product Research, 2024)

Seasonal landscape variability advances Lantian hominin's recognition capacity to strategically adapt to changing environments - Hong Wang; Hao Li; Yahui Qiu; Peixian Shu; Yingna Liu; Weiguo Liu; Jimin Sun; Shuisheng Du; Jing Wang; Stanley H. Ambrose (Quaternary Science Reviews, 2024)

Anti-inflammatory discovery of sesquiterpenoids and a jasmonic acid derivative from Artemisia stolonifera - Ting Wu; Wen-Jing Wang; Zhou-Yuan Li; Yi-Tian Liu; Tian-Ping Yu; Shuang-Ge Li; Hong-Zhi Du; Chun Gui; Da-Hui Liu; Xiao-Long Yang (Phytochemistry, 2024)

Prevalence and characterization of aminoglycoside resistance gene aph(2”)-If-carrying Campylobacter jejuni - Jin Kang; Cheng Zhang; Shuigen Wan; Wenjun Li; Wenbo Zhao; Longyu Li; Yanhong Shang; Xiang-Dang Du; Dejun Liu; Hong Yao (International Journal of Food Microbiology, 2024)

Improvement of thermostability by increasing rigidity in the finger regions and flexibility in the catalytic pocket area of Pseudoalteromonas porphyrae κ-carrageenase - Zeping Du; Xiaoyi Huang; Hebin Li; Mingjing Zheng; Tao Hong; Zhipeng Li; Xiping Du; Zedong Jiang; Hui Ni; Qingbiao Li; Yanbing Zhu (World Journal of Microbiology and Biotechnology, 2024)

Examination of wnt signaling mediated melanin transport and shell color formation in Pacific oyster (Crassostrea gigas) - Yue Min; Qi Li; Hong Yu; Shaojun Du (Marine Life Science & Technology, 2024)
Mollusca exhibit remarkable diversity in shell coloration, attributed to the presence of melanin, a widely distributed pigment with various essential roles, such as mechanical strengthening, antioxidation and thermoregulation. However, the regulatory network governing melanogenesis and melanin transport in molluscs remains poorly understood. In this study, we conducted a systematic analysis of melanin distribution and transport in the Pacific oyster, utilizing light microscopy and high-resolution transmission electron microscopy. In addition, we characterized CgWnt1 and CgWnt2b-a in Crassostrea gigas, and analyzed Wnt signaling in melanocyte formation. Expression analysis revealed that these genes were predominantly expressed in the mantle of black-shelled individuals, particularly in the outer fold of the mantle. Furthermore, we employed RNA interference and inhibitors to specifically inhibit Wnt signaling in both in vivo and in vitro. The results revealed impaired melanogenesis and diminished tyrosinase activity upon Wnt signaling inhibition. These findings suggest the crucial role of Wnt ligands and downstream factors in melanogenesis. In summary, our study provides valuable insights into the regulatory mechanism of shell pigmentation in C. gigas . By demonstrating the promotion of melanogenesis through Wnt signaling modulation, we contribute to a better understanding of the complex processes underlying molluscan melanin production and shell coloration.

α-Fe2O3 nanorods on CoFe-LDH@MX via interfacial interactions for Congo red removal: Experimental and mechanistic studies - Xianyong Hong; Mingxing Shi; Linrui Li; Zhoutian Ding; Zhiren Zhao; Ping Du; Mingzhu Xia; Fengyun Wang (Journal of Environmental Chemical Engineering, 2024)

Associations between exposure to phthalates and liver function among women undergoing assisted reproductive technology - Yi Wang; Li Yin; Yao-Yao Du; Hong-Mei Liao; Juan Li; Wen Yao; Xiao-Qiong Yuan; Qing-Chun Guo; Tao-Ran Deng; Na Guo; Min Zhang; Qiang Zeng; et al. (Environmental Toxicology and Pharmacology, 2024)

Stepwise extraction of Fe, Si from copper slag and self-assembly synthesis of microspheres for As(V) removal: Resource transformation and environmental governance - Donghui Chen; Hong Li; Jie Tan; Dongyun Du; Wei Zhan (Chemical Engineering Journal, 2024)

Industry chain and challenges of microalgal food industry-a review - Yuanhao Chen; Honghao Liang; Hong Du; Valentina Jesumani; Weiling He; Kit-Leong Cheong; Tangcheng Li; Ting Hong (Critical Reviews in Food Science and Nutrition, 2024)

Temporal variations of biological nitrogen fixation and diazotrophic communities associated with artificial seaweed farms - Pengbing Pei; Muhammad Aslam; Chunyou Yang; Peilin Ye; Xiao Ke; Zhanhua Liang; Tangcheng Li; Weizhou Chen; Hong Du (Frontiers in Marine Science, 2024)
Diazotrophic communities contribute inorganic nitrogen for the primary productivity of the marine environment by biological nitrogen fixation (BNF). They play a vital role in the biogeochemical cycle of nitrogen in the marine ecological environment. However, there is still an incomplete understanding of BNF and diazotrophs in artificial seaweed farms. Therefore, this study comprehensively investigated the temporal variations of BNF associated with Gracilariopsis lemaneiformis , as well as the diazotrophic communities associated with macroalgae and its surrounding seawater. Our results revealed that a total of 13 strains belonging to Proteobacteria and Bacteroidetes were identified as N 2 -fixing bacteria using azotobacter selective solid medium and nifH gene cloning. Subsequently, BNF and diazotrophic communities were characterized using the acetylene reduction method and high-throughput sequencing of the nifH gene, respectively. The results showed that nitrogenase activity and nifH gene abundance of epiphytic bacteria on G. lemaneiformis varied significantly among four different cultivation periods, i.e., Cultivation Jan. (CJ), Cultivation Feb. (CF), Cultivation Mar. (CM), Cultivation Apr. (CA). Among them, the nitrogenase activity and nifH gene abundance of epiphytic bacteria on G. lemaneiformis in CM were significantly higher than those in CJ, CF, and CA, indicating that the BNF of eiphytic bacteria on G. lemaneiformis was markedly enhanced. Combined with the data on environmental factors, it was found that the low concentration of nitrogen and phosphorus in CM might considerably boost the BNF of epiphytic bacteria in G. lemaneiformis . The sequencing results of the nifH gene showed that the α-diversity of diazotrophic communities associated with G. lemaneiformis and seawater in CM was higher than that in other cultivation periods. In addition, the diazotrophic communities on G. lemaneiformis were significantly different in CJ, CF, CM, and CA, and they were significantly diverse from diazotrophic communities in seawater. LEfSe analysis indicated that Rhodobacterales, Hyphomonadaceae, Robiginitomaculum , and Robiginitomaculum antarcticum within α-proteobacteria played a remarkable role in BNF in response to nitrogen nutrient deficiency. Taken together, these results provide a unique insight into the interaction between macroalgae and its epiphytic bacteria and lay a foundation for further research on the mechanism of action of nitrogen-cycling microorganisms associated with macroalgae.

Microbial safety evaluation for recycling of sand-filter backwash water in a water plant in Southern China - Ting Xie; Yiming Xu; Xinyu Liu; Caifang Jiang; Hong Liang; Shaogang Liu; Hanchun Du; Shuilan Li; Huiyu Dong; Zhimin Qiang (Journal of Water Process Engineering, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Analysis of factors influencing the energy efficiency in Chinese wastewater treatment plants through machine learning and SHapley Additive exPlanations - Jinze Li; Zexuan Du; Junyan Liu; Linji Xu; Li-ping He; Li Gu; Hong Cheng; Qiang He (Science of The Total Environment, 2024)

An efficient method of preparing Si–Fe–Al–Ca alloy from coal gasification fine slag via plasma smelting and alternating current magnetic field - Yaoxuan Wang; Haiyu Li; Zhaoyang Zhang; Xiaolin Guo; Hongbing Du; Hong Wang; Yanxin Zhuang; Pengfei Xing (Journal of Environmental Management, 2024)

Molecular mechanism of efficient degradation of TPM dyes by Serratia species WKD at high temperature - Yi Wei; Xin-Jiao Dong; Gang Li; Huan Wu; Lin-Na Du; Jia-Cheng Zhou; Jun Zhang; Yan-Ping Xiao; Yue-Mei Shang; Hong-Xia Liu (International Biodeterioration & Biodegradation, 2024)

A recipe for making potassium-rich magmas in collisional orogens: New insights from K and Fe isotopes - De-Hong Du; Xiang-Long Luo; Xiao-Lei Wang; Martin R. Palmer; E.Yalçın Ersoy; Weiqiang Li (Earth and Planetary Science Letters, 2024)

Radial growth responses of Larix gmelinii to drought events in dry and wet areas of northern temperate forests - Haibo Du; Lulu Xu; J. Julio Camarero; Paolo Cherubini; Mai-He Li; Hong S. He; Xiangjun Meng; Zhengfang Wu (Dendrochronologia, 2024)

Performance boosting by induction heating for hydrolysis of carbonyl sulfide using magnetic ordered mesoporous alumina as catalyst - Chao Huang; Yunchuan Hong; Binchen Wu; Hongchao Yu; Xiangqian Du; Min Pan; Weiyi Fan; Fei Gao; Feng Wu; Yixin Zhong; Lin Li; Guoshu Deng; et al. (Chemical Engineering Journal, 2024)

Enhanced electro-optical properties of polymer-dispersed liquid crystals co-doped with fluorescent molecules and nanoparticles for multifunctional applications - Yinfu Lu; Dongliang Yang; Hong Gao; Xin Du; Yuzhen Zhao; Dong Wang; Zemin He; Zongcheng Miao; Hui Cao; Zhou Yang; Wanli He; Yuzhan Li (Chemical Engineering Journal, 2024)

Bacoside a inhibits the growth of glioma by promoting apoptosis and autophagy in U251 and U87 cells - Hai-Yun Liu; Yu-Long Ji; Hong Du; Shu-Hui Chen; Da-Peng Wang; Qiao-Li Lv (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Recovery of alkali in Gracilaria agar production by electrodialysis and membrane concentration - Shanyu Xie; Shuai Zhong; Juan Wang; Jinfang Chen; Lijun Li; Xiping Du; Tao Hong; Mingjing Zheng; Yanbing Zhu; Wei Yin; Qingbiao Li; Hui Ni; et al. (Algal Research, 2024)

Physiological and transcriptome analysis of acclimatory response to cold stress in marine red alga Pyropia yezoensis - Li-Hong Ma; Lin Tian; Yu-Qing Wang; Cong-Ying Xie; Guo-Ying Du (Algae, 2024)
Red macroalga Pyropia yezoensis is a high valuable cultivated marine crop. Its acclimation to cold stress is especially important for long cultivation period across winter in coasts of warm temperate zone in East Asia. In this study, the response of P. yezoensis thalli to low temperature was analyzed on physiology and transcriptome level, to explore its acclimation mechanism to cold stress. The results showed that the practical photosynthesis activity (indicated by ΦPSII and qP) was depressed and pigment allophycocyanin content was decreased during the cold stress of 48 h. However, the Fv/Fm and non-photochemical quenching increased significantly after 24 h, and the average growth rate of thalli also rebounded from 24 to 48 h, indicating a certain extent of acclimation to cold stress. On transcriptionally, the low temperature promoted the expression of differentially expressed genes (DEGs) related to carbohydrate metabolism and energy metabolism, while genes related to photosynthetic system were depressed. The increased expression of DEGs involved in ribosomal biogenesis and lipid metabolism which could accelerate protein synthesis and enhance the degree of fatty acid unsaturation, might help P. yezoensis thallus cells to cope with cold stress. Further co-expression network analysis revealed differential expression trends along with stress time, and corresponding hub genes play important roles in the systemic acquired acclimation to cold stress. This study provides basic mechanisms of P. yezoensis acclimation to cold temperature and may aid in exploration of functional genes for genetic breeding of economic macroalgae.

Silica nanoparticles conferring resistance to bacterial wilt in peanut (Arachis hypogaea L.) - Quanqing Deng; Suihua Huang; Hao Liu; Qing Lu; Puxuan Du; Haifen Li; Shaoxiong Li; Haiyan Liu; Runfeng Wang; Lu Huang; Dayuan Sun; Yahui Wu; et al. (Science of The Total Environment, 2024)

Pigmentiphaga kullae CHJ604 improved the growth of tobacco by degrading allelochemicals and xenobiotics in continuous cropping obstacles - Jia-Xi Xiong; Ling-Shan Du; Na-Na Li; Xiu-Ting Wu; Yang Xiang; Sha Li; Lei Zou; Dongqi Liu; Duo Huang; Ze Feng Xie; Ying Wang; Jinhua Li; et al. (Journal of Hazardous Materials, 2024)

Physiological responses of low- and high-cadmium accumulating Robinia pseudoacacia-rhizobium symbioses to cadmium stress - Lan Gao; Shufeng Wang; Dongchen Zou; Xu Fan; Pan Guo; Hongxia Du; Wancang Zhao; Qiaozhi Mao; Hong Li; Ming Ma; Heinz Rennenberg (Environmental Pollution, 2024)

Numerical modeling of elastic waves using the random-enhanced QPSO algorithm - Meng-quan Zhu; Zhi-yang Wang; Hong Liu; You-ming Li; Du-li Yu (Applied Geophysics, 2024)

Sand fixation and human activities on the Qinghai-Tibet Plateau for ecological conservation and sustainable development - Xiaohong Deng; Heqiang Du; Zongxing Li; Hong Chen; Nan Ma; Yulin Song; Lihui Luo; Quntao Duan (Science of The Total Environment, 2024)

Compositional changes with incremental growth of the Quxu granite batholith, southern Tibet: Evidence from geochronology and geochemistry - Ying-Ze Zhang; Xiao-Lei Wang; Yue Guan; Xiu-Mian Hu; Jun-Yong Li; De-Hong Du; Di Wang (Lithos, 2024)

Tracing magmatic differentiation of peralkaline granites by using K stable isotopes - Hang Xu; Weiqiang Li; Xiao-Lei Wang; Jun Mu; De-Hong Du; Jiao-Long Zhao; Ding-Yi Xiong (Geochimica et Cosmochimica Acta, 2024)

Mechanistic study on levoglucosan condensation and decomposition in the condensed phase during cellulose pyrolysis - Erwei Leng; Li Yang; Tiantian Wang; Sijie Du; Hong Tian; Shan Cheng; Yun Yu (Fuel, 2024)

Attentional impairment and altered brain activity in healthcare workers after mild COVID-19 - Keyi Lin; Yaotian Gao; Wei Ji; Yan Li; Wei Wang; Mengcheng Du; Jia Liu; Zhengyu Hong; Tao Jiang; Yuyang Wang (Brain Imaging and Behavior, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) is highly transmissible and pathogenic. Patients with mild cases account for the majority of those infected with coronavirus disease 2019 (COVID-19). Although there is evidence that many patients with COVID-19 have varying degrees of attentional impairment, little is known about how SARS-COV-2 affects attentional function. This study included a high-risk healthcare population divided into groups of healthcare workers (HCWs) with mild COVID-19 (patient group, n = 45) and matched healthy HCWs controls (HC group, n = 42), who completed general neuropsychological background tests and Attention Network Test (ANT), and underwent resting-state functional magnetic resonance imaging (rs-fMRI) using amplitude of low-frequency fluctuation (ALFF) to assess altered brain activity; Selective impairment occurred in orienting and executive control networks, but not in alert network, in the patient group, and widespread cognitive impairment encompassing general attention, memory, and executive dysfunction. Moreover, the patient group had significantly lower ALFF values in the left superior and left middle frontal gyri than the HC group. SARS-COV-2 infection may have led to reduced brain activity in the left superior and left middle frontal gyri, thus impairing attentional orienting and executive control networks, which may explain the development of attentional deficits after COVID-19.

China's subtropical deciduous plants are more sensitive to climate change than evergreen plants by flowering phenology - Hong‐Li Li; Arshad Ali; Xu Luo; Ke Liao; Nan Sun; Ming‐Shan Xu; Long‐Bin Sha; Dong He; Yan‐Jun Du; Wei‐Wei Sun; Xiao‐Dong Yang (Global Change Biology, 2024)
The ongoing climate change‐induced shifts in flowering phenology have emerged as a consequential force impacting biodiversity and ecosystems. Despite the globally recognized significance of flowering phenology as a key reproductive attribute, studies in subtropical regions have been relatively fewer, particularly in comparison to temperate and cold regions. Additionally, the nuanced response of deciduous and evergreen plants to climate change remains insufficiently explored. In addressing this gap, we built a phenological model and a generalized linear mixed effect model to assess the differential responses of key flowering phenological traits, that is, first flowering date (FFD), peak flowering date (PFD), end of flowering date (EFD), and flowering duration (FD), to climate factors (temperature and precipitation) between deciduous and evergreen plants. We observed distinct responses in flowering phenological traits to climate change between deciduous and evergreen plants. Specifically, the advancement of FFD, PFD, and EFD in deciduous in response to temperature rise exceeded that in evergreen plants. FD in evergreen plants exhibited a stronger extension to temperature increase compared to deciduous. Conversely, the phenological change of evergreen plants in response to decreasing precipitation was greater than that of deciduous ones. Since temperature is a decisive climatic factor in affecting phenological changes, climate change‐induced advances in flowering phenology of deciduous plants are still larger than evergreen plants. Projections from our phenological model under future climate scenarios (SSP 1‐2.6 and SSP 5‐8.5) indicate a continuous enlargement of difference in flowering phenology between deciduous and evergreen plants, with this trend escalating into the future (2100>2070>2050>2030). The larger extension in FD of evergreens to climate change suggests a potential increase in their proportion within subtropical forest communities relative to deciduous plants. These insights contribute significantly to our understanding of the intricate dynamics of climate‐induced changes in subtropical plant ecosystems.

Quantifying landscape connectivity gaps between protected area and natural habitat - Haowei Mu; Shanchuan Guo; Xuecao Li; Yuyu Zhou; Yihe Lü; Xiaoping Du; Jianxi Huang; Chaode Ma; Xingang Zhang; Zilong Xia; Hong Fang; Peijun Du (Journal of Cleaner Production, 2024)

Extreme Sn isotope fractionation in highly evolved granites - Ke-Ke Sun; Jia-Xin She; De-Hong Du; Weiqiang Li; Jun Deng (Chemical Geology, 2024)

Digital mapping of cultivated land soil organic matter in hill-mountain and plain regions - Hongxia Xie; Weiyou Li; Liangxia Duan; Hong Yuan; Qing Zhou; Zhe Luo; Huihui Du (Journal of Soils and Sediments, 2024)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

Seismic performance of prefabricated replaceable graded-yielding energy-dissipating connectors - Fangyu Li; Yongfeng Du; Na Hong; Hu Li; Peihong Chi (Engineering Structures, 2023)

Growth responses to climate warming and their physiological mechanisms differ between mature and young larch trees in a boreal permafrost region - Xi Qi; Paolo Cherubini; Kerstin Treydte; Mai-He Li; Zhengfang Wu; Hong S. He; Haibo Du; Keyan Fang; Matthias Saurer (Agricultural and Forest Meteorology, 2023)

Role of myo-inositol in acute kidney injury induced by cisplatin - Yu-Hong Xie; Ling Wang; Ming-Liang Li; Zhi-Cheng Gong; Jie Du (Toxicology, 2023)

Peracetic acid combined with ultraviolet for ibuprofen degradation: Activation mechanism and reactive species contribution - Gongduan Fan; Yujian Li; Banghao Du; Lei Yao; Chenjian Cai; Hao Li; Shoubin Chen; Jianyong Zou; Zhanglin Hong; Kai-Qin Xu (Process Safety and Environmental Protection, 2023)

Urban vegetation cooling capacity was enhanced under rapid urbanization in China - Chengcong Wang; Zhibin Ren; Yunxia Du; Yujie Guo; Peng Zhang; Guodong Wang; Shengyang Hong; Zijun Ma; Wenhai Hong; Ting Li (Journal of Cleaner Production, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Tailor-made yolk-shell nanocomposites of star-shape Au and porous organic polymer for nitrogen electroreduction to ammonia - Hongming He; Hao-Ming Wen; Ping Li; Hong-Kai Li; Cheng-Peng Li; Zhihong Zhang; Miao Du (Chemical Engineering Journal, 2023)

Improved sequential production of hydrogen and caproate by addition of biochar prepared from cornstalk residues - Jian Du; Pian-Pian Xu; Hong-Yu Ren; Guang-Li Cao; Guo-Jun Xie; Nan-Qi Ren; Bing-Feng Liu (Bioresource Technology, 2023)

Developing thermal prediction models for the elderly under temperature step changes - Shan Zhou; Baizhan Li; Chenqiu Du; Runming Yao; Linyuan Ouyang; Haixia Zhou; Risto Kosonen; Arsen Krikor Melikov; Liangyue Shang; Hong Liu (Building and Environment, 2023)

Ångstrom-scale silver particles ameliorate collagen-induced and K/BxN-transfer arthritis in mice via the suppression of inflammation and osteoclastogenesis - Ze-Hui He; Jing-Tao Zou; Xia Chen; Jiang-Shan Gong; Ya Chen; Ling Jin; Yi-Wei Liu; Shan-Shan Rao; Hao Yin; Yi-Juan Tan; Zun Wang; Wei Du; et al. (Inflammation Research, 2023)

Environmental exposure and ecological risk of perfluorinated substances (PFASs) in the Shaying River Basin, China - Ya-Hui Zhang; Ting-Ting Ding; Zi-Yan Huang; Hong-Yi Liang; Shi-Lin Du; Jin Zhang; Hui-Xian Li (Chemosphere, 2023)

Environmental irradiance and nitrogen source variability trigger the intracellular carbon and nitrogen reallocation of Gracilariopsis lemaneiformis (Rhodophyta) - Tangcheng Li; Yang Jiang; Senjie Lin; Sien Zhong; Shujuan Jian; Weizhou Chen; Hong Du (Aquaculture, 2023)

Cytological observations in abortion formation and morphological character of pollen in seedless chestnut rose (Rosa sterilis) - Qian Du; Kui Zhou; Siling Zhong; Changying Li; Jinbu Fan; Qian Wang; Yi Hong; Xiaopeng Wen (Flora, 2023)

Benzeneboronic−alginate/quaternized chitosan−catechol powder with rapid self-gelation, wet adhesion, biodegradation and antibacterial activity for non-compressible hemorrhage control - Yan Du; Xingtao Chen; Lin Li; Heng Zheng; Aiping Yang; Hong Li; Guoyu Lv (Carbohydrate Polymers, 2023)

Observed and projected changes in wet and dry spells for the major river basins in East Asia - Lirong Huang; Haibo Du; Yongcai Dang; Hong S. He; Lei Wang; Risu Na; Na Li; Zhengfang Wu (International Journal of Climatology, 2023)
Spatiotemporal changes in wet and dry spells had significantly contributed to climate‐related natural hazards in East Asia, especially in river basins undergoing warming. However, few studies have systematically analysed these changes for river basins at different latitudes. Herein, we investigated the observed and projected variations in wet and dry spells for East Asian river basins at different latitudes. We found that river basins at low latitudes (Yangtze and Pearl rivers) had obvious wet characteristics, whereas those at high latitudes (Amur and Yellow rivers) had obvious dry characteristics. In general, the river basins presented a ‘wet south but dry north’ spatial pattern. Long‐duration wet spells have been shown to be the primary contributor to total wet spells in low‐latitude river basins, while long‐duration dry spells have been found to be the primary contributor to total dry spells in high‐latitude river basins. Importantly, climate is changing from prolonged wet spells to short, intense wet spells in low‐latitude river basins, whereas the climate is changing from single, short dry spells to moderate, prolonged dry spells at high latitudes. These changes indicate a high probability of flash floods in river basins at low latitudes and a high probability of droughts at high latitudes. In the future, more temporally clustered heavy precipitation events and prolonged dry spells may lead to increasingly uneven precipitation in high‐latitude river basins and the Pearl River basin, especially under the higher shared socioeconomic pathway scenarios. In contrast, more frequent consecutive heavy precipitation events may aggravate the risk of flooding in the Yangtze River basin. These findings are expected to serve as a guide for flood and drought risk mitigation in East Asia under a warming climate.

Effects of salinity on methane emissions and methanogenic archaeal communities in different habitat of saline-alkali wetlands - Feng Li; Huiju Li; Huihui Su; Wei Du; Zhongyan Gao; Huajun Liu; Hong Liang; Dawen Gao (Environmental Science and Pollution Research, 2023)

Enzyme immobilization as a sustainable approach toward ecological remediation of organic-contaminated soils: Advances, issues, and future perspectives - Litao Wang; Xuran Du; Ying Li; Yuhong Bai; Teng Tang; Jing Wu; Hong Liang; Dawen Gao (Critical Reviews in Environmental Science and Technology, 2023)

Vegetation structural shift tells environmental changes on the Tibetan Plateau over 40 years - Yanfen Wang; Kai Xue; Ronghai Hu; Boyang Ding; Hong Zeng; Ruijin Li; Bin Xu; Zhe Pang; Xiaoning Song; Congjia Li; Jianqing Du; Xiuchun Yang; et al. (Science Bulletin, 2023)

From arc accretion to within-plate extension: Geochronology and geochemistry of the Neoproterozoic magmatism on the northern margin of the Yangtze Block - Yu Huang; Xiao-Lei Wang; Jun-Yong Li; Ru-Cao Li; De-Hong Du; Chang-Hong Jiang; Lin-Sen Li; Ning Ding (Precambrian Research, 2023)

C21 steroids from the roots of Marsdenia tenacissima - Jin-Ling Liu; Hong-Tao Xu; Dan-Dan Mu; Xiao Han; Ting-Ting Du; Yong-li Wang; Xiao-Hui Wei; Gui-Xin Chou (Phytochemistry, 2023)

Effects of epigallocatechin-3-gallate on the structural hierarchy of the gluten network in dough - Chong Chong Wang; Zheng Sheng; Ya Hui Zhang; Qi Zhen Du; Qin Li; Pen Jin; Dong Chao Xie; Wei Hong Min; Hai Hua Zhang (Food Hydrocolloids, 2023)

High-throughput and high-performance lithium-ion batteries via dry processing - Runming Tao; Bryan Steinhoff; Xiao-Guang Sun; Kahla Sardo; Brendan Skelly; Harry M. Meyer; Conrad Sawicki; Georgios Polizos; Xiang Lyu; Zhijia Du; Jun Yang; Kunlun Hong; et al. (Chemical Engineering Journal, 2023)

Different behaviors in nitrogen leaching between soil types following the substitution of synthetic fertilizers by manure - Xinzhong Du; Yitao Zhang; Jungai Li; Chang Peng; Hongyuan Wang; Muhammad Amjad Bashir; Zhen Wang; Limei Zhai; Hong J. Di; Hongbin Liu (Nutrient Cycling in Agroecosystems, 2023)

Detection of depression marker ASS1 in urine by gold nanoparticles based dual epitope-peptides imprinted sensor - Hong Wei; Zixia Wang; Yanping Wang; Jing Ma; Yan Chen; Min Guo; Yuanyuan Li; Yongling Du; Fangdi Hu (Analytica Chimica Acta, 2023)

Martynoside rescues 5-fluorouracil-impaired ribosome biogenesis by stabilizing RPL27A - Mengying Hong; Yushen Du; Dongdong Chen; Yuan Shi; Menglong Hu; Kejun Tang; Zhuping Hong; Xiangzhi Meng; Wan Xu; Gaoqi Wu; Yuanyuan Yao; Liubo Chen; et al. (Science Bulletin, 2023)

Endocrine-disrupting chemicals and autoimmune diseases - Rong-Gui Huang; Xian-Bao Li; Yi-Yu Wang; Hong Wu; Kai-Di Li; Xue Jin; Yu-Jie Du; Hua Wang; Fang-Yi Qian; Bao-Zhu Li (Environmental Research, 2023)

High-resolution Re-Os isotope stratigraphy, and geochemical fingerprints identification of Late Ordovician–Early Silurian strata in northern Guizhou, China: Implications for LOME and environmental changes - Xinwei Li; Chao Li; Xiaojun Jiang; Hong Zhao; Limin Zhou; Wenjun Qu; Andao Du (Earth-Science Reviews, 2023)

Performance enhancement of white rot fungi extracellular enzymes via new hydrogel microenvironments for remediation of benzo[a]pyrene contaminated soil - Litao Wang; Ying Li; Xuran Du; Jing Wu; Zhou Zhang; Huixia Jin; Hong Liang; Dawen Gao (Journal of Hazardous Materials, 2023)

Chronic exposure to (2 R,6 R)-hydroxynorketamine induces developmental neurotoxicity in hESC-derived cerebral organoids - Zhulin Du; Zhenle Zang; Jing Luo; Tianyao Liu; Ling Yang; Yun Cai; Liuyongwei Wang; Dandan Zhang; Jinghui Zhao; Junwei Gao; Keyi Lv; Lian Wang; et al. (Journal of Hazardous Materials, 2023)

A novel process to recycle coal gasification fine slag by preparing Si-Fe-Al-Ca alloy - Yaoxuan Wang; Zhaoyang Zhang; Lamei Li; Xiaolin Guo; Donghui Wei; Jian Kong; Hongbing Du; Hong Wang; Yanxin Zhuang; Pengfei Xing (Journal of Environmental Management, 2023)

Adaptive fuzzy control of underwater vehicle manipulator system with dead-zone band input nonlinearities via fuzzy performance and disturbance observers - Hong-Du Wang; Yun-Xiang Zhai; Umer Hameed Shah; Mansour Karkoub; Ming Li (Ocean Engineering, 2023)

A novel resourcezation strategy for the alkylphenol distillation residues: From hazardous wastes to high-valued epoxy asphalt materials - Yuansen Li; Lin He; Jinze Du; Hong Sui; Xingang Li (Journal of Cleaner Production, 2023)

Novel dual Z-scheme Ag-bridged AgI/FeVO4-C3N4 plasmonic heterojunction: A study on the performance and mechanism of photocatalytic reduction of Cr(VI) - Guoxiang Yang; Longyang Wang; Shuzhen Zheng; Hong Wu; Derek Hao; Qiang Li; Hao Du; Hiromi Yamashita; Qi Wang (Journal of Environmental Chemical Engineering, 2023)

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Transportation decarbonization requires life cycle-based regulations: Evidence from China’s passenger vehicle sector - Xingyu Xue; Xin Sun; Hongrui Ma; Jianxin Li; Frank T. Hong; Sha Du (Transportation Research Part D: Transport and Environment, 2023)

Deyeuxia angustifolia upward migration and nitrogen deposition change soil microbial community structure in an alpine tundra - Na Li; Haibo Du; Mai-He Li; Risu Na; Renkai Dong; Hong S. He; Shengwei Zong; Lirong Huang; Zhengfang Wu (Soil Biology and Biochemistry, 2023)

Occam’s Razor-Inspired Nb2C delivery platform potentiates breast cancer therapy and inhibits lung metastasis - Xiangping Lin; Zhongjun Li; Shuang Du; Qun Wang; Yucheng Guan; Guopan Cheng; Huijie Hong; Jianqing Li; Xiaojia Chen; Tongkai Chen (Chemical Engineering Journal, 2023)

Ultralight, robust, and high Prussian blue-loading polyacrylonitrile aerogel: Preparation, characterization and efficient adsorption/removal of Cs+ - Xiao-Bo Yang; Wei Li; Ze-Zhong Lin; Jing-Qi Liu; Hong-Xin Jiang; Hao Jia; Wei-Liang Jin; Xin-Long Hou; Bing-Xuan Du; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

Mediation of self-concept clarity and self-control between negative emotional states and emotional eating in Chinese adolescents - Guangcan Xiang; Qingqing Li; Yao Xiao; Yong Liu; Xiaoli Du; Yanyan He; Hong Chen (Appetite, 2023)

A comprehensive understanding of adaptive thermal comfort in dynamic environments – An interaction matrix-based path analysis modeling framework - Ru Ming; Baizhan Li; Chenqiu Du; Wei Yu; Hong Liu; Risto Kosonen; Runming Yao (Energy and Buildings, 2023)

Synergistic strategy design of (malonamide-amidoxime) bifunctional branching network crosslinked membrane and application in uranium (VI) resource recovery - Yang Li; Qi Ren; Rong Hua; Hong-Tao Xia; Xu-Xin Li; Ze-Yang Wang; Xuan Fu; Yan-Jun Du; Ze-Yi Yan; Yun Wang (Chemical Engineering Journal, 2023)

Phytochemical and chemotaxonomic investigations on the aerial parts of Cynanchum auriculatum Royle ex Wight - Yanling Xu; Chenyang Wu; Lu Wang; Shengbo Wu; Yueru Chen; Xiaoxue Ding; Lin Wang; Yi Yu; Weiming Du; Yuqing Zhang; Rachel Y.H. Yang; Jian Hong; et al. (Biochemical Systematics and Ecology, 2023)

Gli2-induced lncRNA Peg13 alleviates cerebral ischemia-reperfusion injury by suppressing Yy1 transcription in a PRC2 complex-dependent manner - Yanling Li; Chuntian Liu; Hong Fan; Yun Du; Ru Zhang; Shuqin Zhan; Guilian Zhang; Ning Bu (Metabolic Brain Disease, 2023)

Nematicidal phytochemicals against pine wood nematode, Bursaphelenchus xylophilus (nematoda: aphelenchoididae) - Jiale Feng; Ronggui Li; Chao Wang; Hong Yang; Wenjun Deng; Guicai Du; Qunqun Guo (Journal of Plant Diseases and Protection, 2023)

[Cuproptosis-related immune gene signature predicts clinical benefits from anti-PD-1/PD-L1 therapy in non-small-cell lung cancer - Linfeng Luo; Anlin Li; Sha Fu; Wei Du; Li-Na He; Xuanye Zhang; Yixing Wang; Yixin Zhou; Yang Yunpeng; Zhang Li; Shaodong Hong (Immunologic Research, 2023)

Emergence of lnu(C) variant conferring lincomycin resistance in Campylobacter coli of chicken origin - Wenjun Li; Dian Jiao; Jin Kang; Runhao Yu; Wenbo Zhao; Chunyan Xu; Ruichao Li; Xiang-Dang Du; Hong Yao (International Journal of Food Microbiology, 2023)

Cooperative adsorption-degradation of benzo[a]pyrene by extracellular enzymes of white rot fungi immobilized on macroporous adsorption resin - Xuran Du; Litao Wang; Ying Li; Jing Wu; Guanyu Chen; Hong Liang; Dawen Gao (International Biodeterioration & Biodegradation, 2023)

Changes in the functional properties of casein conjugates prepared by Maillard reaction with pectin or arabinogalactan - Siqi Yang; Guofang Zhang; Hong Chu; Peng Du; Aili Li; Libo Liu; Chun Li (Food Research International, 2023)

Multiple effects of visual-acoustic-thermal perceptions on the overall comfort of elderly adults in residential outdoor environments - Meng Du; Bo Hong; Chujian Gu; Yichen Li; Yayun Wang (Energy and Buildings, 2023)

A chromosome-scale genome sequence of sudangrass (Sorghum sudanense) highlights the genome evolution and regulation of dhurrin biosynthesis - Jieqin Li; Lihua Wang; Paul W. Bible; Wenmiao Tu; Jian Zheng; Peng Jin; Yanlong Liu; Junli Du; Jiacheng Zheng; Yi-Hong Wang; Qiuwen Zhan (Theoretical and Applied Genetics, 2023)

2000 years of lake-level fluctuations and human adaptation around China's largest freshwater lake - Huanye Wang; Weiguo Liu; Qin Leng; Lin Yang; Hui Zhao; Jun Yang; Yuwei Chen; Shangbin Xiao; Yunning Cao; Jing Hu; Xiaoke Qiang; Peng Cheng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Proteomic Differences Between the Ovulatory and Anovulatory Sides of the Mare's Follicular and Oviduct Fluid - Yingchao Shen; Tseweendolmaa Ulaangerel; Hong Ren; Toli Davshilt; Minna Yi; Xinyu Li; Jingya Xing; Ming Du; Dongyi Bai; Manglai Dugarjav; Gerelchimeg Bou (Journal of Equine Veterinary Science, 2023)

Early Cretaceous palynofloras from the Bongor basin, Chad, and their palaeoenvironmental and palaeoclimatic significances - Ying Hu; Jie Hu; Yebo Du; Huinan Lu; Ning Yang; Li Wang; Hong-He Xu (Journal of African Earth Sciences, 2023)

Octenyl succinate anhydride debranched starch-based nanocarriers for curcumin with improved stability and antioxidant activity - Shangyun Liang; Jing Du; Yan Hong; Li Cheng; Zhengbiao Gu; Zhaofeng Li; Caiming Li (Food Hydrocolloids, 2023)

Analysis of the Gridded Influencing Factors of the PM2.5 Concentration in Sichuan Province Based on a Stacked Machine Learning Model - Yuhong Wu; Ning Du; Li Wang; Hong Cai; Bin Zhou (International Journal of Environmental Research, 2023)

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

A repeated dose 28-day oral toxicity study of sodium dehydroacetate (DHA-S) in Wistar rats - Hong-ju Du; Guo-hui Tong; Jun-yu Ning; Shan Gao; Qing Yang; Ying Feng; Peng Zhang; Wei Zhang; Hai-ming Jing; Guo-jun Li (Regulatory Toxicology and Pharmacology, 2023)

Impact of air pollutants on influenza-like illness outpatient visits under urbanization process in the sub-center of Beijing, China - Zhong-Song Zhang; Lu Xi; Li-Li Yang; Xin-Yao Lian; Juan Du; Yan Cui; Hong-Jun Li; Wan-Xue Zhang; Chao Wang; Bei Liu; Yan-Na Yang; Fuqiang Cui; et al. (International Journal of Hygiene and Environmental Health, 2023)

Rapid identification of fish species by laser-induced breakdown spectroscopy and Raman spectroscopy coupled with machine learning methods - Lihui Ren; Ye Tian; Xiaoying Yang; Qi Wang; Leshan Wang; Xin Geng; Kaiqiang Wang; Zengfeng Du; Ying Li; Hong Lin (Food Chemistry, 2023)

Genome-Wide Identification Reveals the Potential Functions of the bZIP Gene Family in Common Bean (Phaseolus vulgaris) in Response to Salt Stress During the Sprouting Stage - Qi Zhang; Wen-jing Zhang; Zhen-gong Yin; Wei-jia Li; Chun-Yang Xia; Hao-Yue Sun; Yi-Ming Yang; Hong-Bin Wu; Shuo Zhang; Hao-hao Zhao; Wen-Hui Zhang; Yong-xia Guo; et al. (Journal of Plant Growth Regulation, 2022)

Role of Mitophagy in neurodegenerative Diseases and potential tagarts for Therapy - Lingling Jiao; Xixun Du; Yong Li; Qian Jiao; Hong Jiang (Molecular Biology Reports, 2022)

Coral bleaching from a nutrient perspective is understudied: A bibliometric survey - Tangcheng Li; Jiahong Huang; Hong Du; Xiaojuan Liu; Chongming Zhong; Senjie Lin (Frontiers in Marine Science, 2022)
How coral–Symbiodiniaceae mutualistic symbiosis is established, maintained, and disrupted is arguably the most fundamental and central area of coral research. The breakdown of this symbiosis, and consequent coral bleaching, have been frequently attributed to thermal stress, although microbial attack and pollution have also been blamed. Despite the perceived intense and broad research, it is unclear whether all the potential causes have been given adequate attention and whether some important areas have been overlooked. This work aims to comprehensively review the literature on coral and Symbiodiniaceae research and provide a portrait of the current coral research landscape, hence identifying areas that require more research effort. Data of publication output were extracted from the Web of Science (WoS) from 1986 to 2022 by using the keywords “coral” and “Symbiodiniaceae.” A total of 43,089 and 3,191 papers in the coral and Symbiodiniaceae were identified, mostly published after 2002. The journal Coral Reefs was ranked first regarding the total number of publications on coral or Symbiodiniaceae. The USA, Australia, and China were the top three countries in the number of publications. The network co-occurrence analysis of all keywords in coral and Symbiodiniaceae using VOSviewer showed that biodiversity, climate change, nutrient, and survival were the central research areas in coral and Symbiodiniaceae. Among them, climate change was the most invested research field, as revealed by the high proportion of published literature, while nutrient was the most understudied area. Thematic evolution analysis revealed that nutrient enrichment combined with elevated temperature was an emerging research field about coral and Symbiodiniaceae. Besides, nitrogen is currently the most studied nutrient. The findings from this study shed light on the trends of coral and Symbiodiniaceae research in the past 36 years, current research hotspots in the field, and areas that need more research investment going forward.

Improving protected area effectiveness through consideration of different human‐pressure baselines - Chun‐Ting Feng; Ming Cao; Fang‐Zheng Liu; Yue Zhou; Jin‐Hong Du; Li‐Bo Zhang; Wen‐Jie Huang; Jian‐Wu Luo; Jun‐Sheng Li; Wei Wang (Conservation Biology, 2022)
Previous assessments of the effectiveness of protected areas (PAs) focused primarily on changes in human pressure over time and did not consider the different human‐pressure baselines of PAs, thereby potentially over‐ or underestimating PA effectiveness. We developed a framework that considers both human‐pressure baseline and change in human pressure over time and assessed the effectiveness of 338 PAs in China from 2010 to 2020. The initial state of human pressure on PAs was taken as the baseline, and changes in human pressure index (HPI) were further analyzed under different baselines. We used the random forest models to identify the management measures that most improved effectiveness in resisting human pressure for the PAs with different baselines. Finally, the relationships between the changes in the HPI and the changes in natural ecosystems in PAs were analyzed with different baselines. Of PAs with low HPI baselines, medium HPI baselines, and high HPI baselines, 76.92% ( n =150), 11.11% ( n =12), and 22.86% ( n =8) , respectively, showed positive effects in resisting human pressure. Overall, ignoring human‐pressure baselines somewhat underestimated the positive effects of PAs, especially for those with low initial human pressure. For PAs with different initial human pressures, different management measures should be taken to improve effectiveness and reduce threats to natural ecosystems. We believe our framework is useful for assessing the effectiveness of PAs globally, and we recommend it be included in the Convention on Biological Diversity Post‐2020 Strategy.

Comprehensive analysis using multiple-integrated techniques on the failure mechanism and dynamic process of a long run-out landslide: Jichang landslide case - Yiding Bao; Hong Wang; Lijun Su; Dajiang Geng; Liang Yang; Peng Shao; Yuchao Li; Ni Du (Natural Hazards, 2022)

Seismic performance evaluation of VCFPB isolated storage tank using real-time hybrid simulation - Hong Yue; Tang Zhenyun; Li Zhenbao; Du Xiuli (Earthquake Engineering and Engineering Vibration, 2022)

Extensive sequence divergence between the reference genomes of Taraxacum kok-saghyz and Taraxacum mongolicum - Tao Lin; Xia Xu; Huilong Du; Xiuli Fan; Qingwen Chen; Chunyan Hai; Zijian Zhou; Xiao Su; Liquan Kou; Qiang Gao; Lingwei Deng; Jinsheng Jiang; et al. (Science China Life Sciences, 2022)

Hyper-SUMOylation of SMN induced by SENP2 deficiency decreases its stability and leads to spinal muscular atrophy-like pathology - Yuhong Zhang; Xu Chen; Qiqi Wang; Congcong Du; Wenbin Lu; Hong Yuan; Zhenzhen Zhang; Danqing Li; Xing Ling; Xiang Ren; Yang Zhao; Qi Su; et al. (Journal of Molecular Medicine, 2021)

Development and characterization of SNP markers in many-lined sun skink (Eutropis multifasciata) from transcriptomic sequences - Youfu Lin; Zijin Qian; Shiyu Shen; Yicheng Huang; Yu Du; Hong Li; Lian Chen (Conservation Genetics Resources, 2021)

Identification of a phage-derived depolymerase specific for KL64 capsule of Klebsiella pneumoniae and its anti-biofilm effect - Min Li; Pei Li; Long Chen; Genglin Guo; Yuyi Xiao; Liang Chen; Hong Du; Wei Zhang (Virus Genes, 2021)

A review on the removal of heavy metals and metalloids by constructed wetlands: bibliometric, removal pathways, and key factors - Guanlong Yu; Peiyuan Li; Guoliang Wang; Jianwu Wang; Yameng Zhang; Shitao Wang; Kai Yang; Chunyan Du; Hong Chen (World Journal of Microbiology and Biotechnology, 2021)

Safety evaluation and ibuprofen removal via an Alternanthera philoxeroides-based biochar - Yuan-da Du; Xin-qian Zhang; Li Shu; Yu Feng; Cui Lv; Hong-qiang Liu; Fei Xu; Qian Wang; Cong-cong Zhao; Qiang Kong (Environmental Science and Pollution Research, 2021)

The rescue and selection of thermally stable type O vaccine candidate strains of foot-and-mouth disease virus - Ya Gao; Pinghua Li; Xueqing Ma; Xingwen Bai; Pu Sun; Ping Du; Hong Yuan; Yimei Cao; Kun Li; Yuanfang Fu; Jing Zhang; Huifang Bao; et al. (Archives of Virology, 2021)

Increasing Temperature Alters the Effects of Extracellular Copper on Thalassiosira Pseudonana Physiology and Transcription - Xinjie Wang; Wang Cao; Hong Du; Wenhua Liu; Ping Li (Journal of Marine Science and Engineering, 2021)
Copper (Cu) is essential for many physiological processes in phytoplankton, including electron-transfer reactions and high-affinity Fe transport systems. However, at high concentrations, Cu can have a toxic effect on phytoplankton. Phytoplankton’s tolerance to certain toxicants in marine ecosystems cannot always be solely attributed to the presence of compounds, as various environmental factors including temperature can also indirectly influence their effects on organisms. In this study, we investigated the effects of different Cu concentrations (0, 19.6, 160, 800, and 8000 nM) on the growth and physiological changes in the centric diatom Thalassiosira pseudonana (CCMP 1335) when simultaneously applied with temperature cultivation of 20 °C and 25 °C. At low (0 nM) and high (8000 nM) Cu concentrations, the growth rate of T. pseudonana was inhibited, though an increase in temperature lessened this inhibition. There were no significant changes in the POC:PON ratio during all of the treatments. However, increasing the temperature significantly decreased the POC: POP, PON: POP and BSi: POP ratios of T. pseudonana. The intracellular Cu content of T. pseudonana varied from 0.13 to 13.28 fg cell−1 in response to increases in ambient Cu concentrations. Lastly, an increase in the Cu concentration decreased the transcriptional expression of CTR (copper transporter), 3Hfcp (photosynthetic protein), and Sit1 (silica shell formation) encoding genes. In conclusion, our results indicated that T. pseudonana can adapt to physiological processes and molecular mechanisms in response to varying Cu concentrations and ambient temperatures.

Neuroprotective triterpene saponins from the leaves of Panax notoginseng - Ji-Wu Huang; Yi-Qian Du; Chuang-Jun Li; Jing-Zhi Yang; Jie Ma; Ying-Da Zang; Nai-Hong Chen; Dong-Ming Zhang (Natural Product Research, 2021)

Lithological and environmental controls on large tafoni along conglomerate cliffs in subtropic humid Danxiashan UNESCO Global Geopark - Xin Chen; Liu-qin Chen; Yan-hong Zhang; Ding-ding Du; Hai-ping Hu; Dong-xing Liu; Wen-zhuo Li (Journal of Mountain Science, 2021)

CRISPR/Cas9 Mediated High Efficiency Knockout of Myosin Essential Light Chain Gene in the Pacific Oyster (Crassostrea Gigas) - Huijuan Li; Hong Yu; Shaojun Du; Qi Li (Marine Biotechnology, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Alternation of soil bacterial and fungal communities by tomato–rice rotation in Hainan Island in Southeast of China - Xiang Ma; Minglun Du; Peng Liu; Yanqiong Tang; Hong Li; Qianhua Yuan; Yunze Ruan; Lei Meng; Jiachao Zhang; Min Lin; Zhu Liu (Archives of Microbiology, 2021)

Essential oil from Artemisia annua aerial parts: composition and repellent activity against two storage pests - Hong Liu; Shan-Shan Guo; Li Lu; Dian Li; Jun Liang; Zhong-Hui Huang; Yan-Mei Zhou; Wen-Juan Zhang; Shushan Du (Natural Product Research, 2021)

TRPM7 Mediates Neuronal Cell Death Upstream of Calcium/Calmodulin-Dependent Protein Kinase II and Calcineurin Mechanism in Neonatal Hypoxic-Ischemic Brain Injury - Ekaterina Turlova; Raymond Wong; Baofeng Xu; Feiya Li; Lida Du; Steven Habbous; F. David Horgen; Andrea Fleig; Zhong-Ping Feng; Hong-Shuo Sun (Translational Stroke Research, 2021)

Study on NOx removal from simulated flue gas by an electrobiofilm reactor: EDTA-ferrous regeneration and biological kinetics mechanism - Nan Liu; Ying-ying Li; Du-juan Ouyang; Rui Guo; Run Chen; Wei Li; Ji-xiang Li; Ji-hong Zhao (Environmental Science and Pollution Research, 2021)

Phylogenetic analysis of infectious bronchitis virus circulating in southern China in 2016–2017 and evaluation of an attenuated strain as a vaccine candidate - Libin Chen; Bin Xiang; Yanfen Hong; Qian Li; Haoyun Du; Qiuyan Lin; Ming Liao; Tao Ren; Chenggang Xu (Archives of Virology, 2021)

Characterization and genome analysis of Klebsiella phage P509, with lytic activity against clinical carbapenem-resistant Klebsiella pneumoniae of the KL64 capsular type - Min Li; Yuyi Xiao; Pei Li; Zitong Wang; Weiling Qi; Zitai Qi; Liang Chen; Hong Du; Wei Zhang (Archives of Virology, 2020)

Single-tube detection of nine bacterial antibiotic-resistance genes by a 2-dimensional multiplex qPCR assay based on fluorescence and melting temperature - Yingxue Li; Ping Xu; Zhenzhou Wan; Hong Du; Xia Jin; Chiyu Zhang (Molecular Biology Reports, 2020)

Comparison of three ultrasonographic examinations on the synovial membrane vascularity of RA patients - Xiuli Jin; Fengjuan Li; Huanyan Liu; Hong Wang; Jianwen Du (Physical and Engineering Sciences in Medicine, 2020)

Litorilituus lipolyticus sp. nov., isolated from intertidal sand of the Yellow Sea in China, and emended description of Colwellia asteriadis - Ang Liu; Yan-Jiao Zhang; Qing-Jie Xue; Hui Wang; Yuan-Yuan Yang; Feng Du; Long-Yu Zhao; Hong-Hua Zhang; Yun-Qing Li; Xiu-Zhen Li (Antonie van Leeuwenhoek, 2020)

One-step generation of zebrafish carrying a conditional knockout-knockin visible switch via CRISPR/Cas9-mediated intron targeting - Jia Li; Hong-Yu Li; Shan-Ye Gu; Hua-Xing Zi; Lai Jiang; Jiu-Lin Du (Science China Life Sciences, 2020)

Neuroprotective Effects of AG490 in Neonatal Hypoxic-Ischemic Brain Injury - Feiya Li; Raymond Wong; Zhengwei Luo; Lida Du; Ekaterina Turlova; Luiz R. G. Britto; Zhong-Ping Feng; Hong-Shuo Sun (Molecular Neurobiology, 2019)

Repellent activities of essential oils rich in sesquiterpenoids from Saussurea amara (L.) DC. and Sigesbeckia pubescens Makino against two stored-product insects - Zhi-Hua Li; Yang Wang; Jian-Sheng Sun; Ji-Gang Li; Ke-Xing Zou; Hong Liu; Gui-Xiang Li; Zhi-Zhong Hu; Li-Zheng Nong; Zhen-Xing Ning; Yan Wu; Shu-Shan Du (Environmental Science and Pollution Research, 2019)

Genome-Wide Identification and Comparative Expression Profile Analysis of the Long-Chain Acyl-CoA synthetase (LACS) Gene Family in Two Different Oil Content Cultivars of Brassica napus - Zhongchun Xiao; Nannan Li; Shufeng Wang; Juanjuan Sun; Liyuan Zhang; Chao Zhang; Hong Yang; Huiyan Zhao; Bo Yang; Lijuan Wei; Hai Du; Cunmin Qu; et al. (Biochemical Genetics, 2019)

Flavivirga rizhaonensis sp. nov., a marine bacterium isolated from intertidal sand - Ang Liu; Hong-Mei Liu; Feng Du; Shuang Wang; Long-Yu Zhao; Hong-Hua Zhang; Yun-Qing Li; Qing-Jie Xue; Xiu-Zhen Li (Antonie van Leeuwenhoek, 2019)

Analysis of cardiovascular disease-related NF-κB-regulated genes and microRNAs in TNFα-treated primary mouse vascular endothelial cells - Hui Zhu; Yun Li; Mao-xian Wang; Ju-hong Wang; Wen-xin Du; Fei Zhou (Journal of Zhejiang University-SCIENCE B, 2019)

Antihyperlipidemic glycosides from the root bark of Lycium chinense - Hui Chen; Yu-Jie Li; Yan-Jun Sun; Xiao-Kun Li; Gong Jian-Hong; Ya Wu; Fang-Yi Su; Kun Du; Yan-Li Zhang; Wei-Sheng Feng (Natural Product Research, 2019)

Opposite effects of winter day and night temperature changes on early phenophases - Fandong Meng; Lirong Zhang; Zhenhua Zhang; Lili Jiang; Yanfen Wang; Jichuang Duan; Qi Wang; Bowen Li; Peipei Liu; Huan Hong; Wangwang Lv; Wangmu Renzeng; et al. (Ecology, 2019)
Changes in day (maximum temperature, T MAX ) and night temperature (minimum temperature, T MIN ) in the preseason (e.g., winter and spring) may have opposite effects on early phenophases (e.g., leafing and flowering) due to changing requirements of chilling accumulations ( CAC ) and heating accumulations ( HAC ), which could cause advance, delay or no change in early phenophases. However, their relative effects on phenology are largely unexplored, especially on the Tibetan Plateau. Here, observations were performed using a warming and cooling experiment in situ through reciprocal transplantation (2008–2010) on the Tibetan Plateau. We found that winter minimum temperature ( T MIN ) warming significantly delayed mean early phenophases by 8.60 d/°C, but winter maximum temperature ( T MAX ) warming advanced them by 12.06 d/°C across six common species. Thus, winter mean temperature warming resulted in a net advance of 3.46 d/°C in early phenophases. In contrast, winter T MIN cooling, on average, significantly advanced early phenophases by 5.12 d/°C, but winter T MAX cooling delayed them by 7.40 d/°C across six common species, resulting in a net delay of 2.28 d/°C for winter mean temperature cooling. The opposing effects of T MAX and T MIN warming on the early phenophases may be mainly caused by decreased CAC due to T MIN warming (5.29 times greater than T MAX ) and increased HAC due to T MAX warming (3.25 times greater than T MIN ), and similar processes apply to T MAX and T MIN cooling. Therefore, our study provides another insight into why some plant phenophases remain unchanged or delayed under climate change.

Chemical composition of essential oils from four Rhododendron species and their repellent activity against three stored-product insects - Li Bai; Mei-Ling Jiao; Hong-Yuan Zang; Shan-Shan Guo; Yang Wang; Yu-Li Sang; Shu-Shan Du (Environmental Science and Pollution Research, 2019)

Targeted Gene Disruption in Pacific Oyster Based on CRISPR/Cas9 Ribonucleoprotein Complexes - Hong Yu; Huijuan Li; Qi Li; Rui Xu; Chenyang Yue; Shaojun Du (Marine Biotechnology, 2019)

Genetic Structure and Haplotype Pattern of Marine Planktonic Ostracod (Porroecia spinirostris) from South China Sea Based on Mitochondrial COI Gene - Lei Xu; Hong Li; Lianggen Wang; Feiyan Du (Ocean Science Journal, 2019)

A chalcone synthase controls the verticillium disease resistance response in both Arabidopsis thaliana and cotton - Kai Jian Lei; Li Zhang; Xiao Yu Du; Yi An; Gai Hong Chang; Guo Yong An (European Journal of Plant Pathology, 2018)

Lack of Association Between DNMT3B Polymorphisms and Sporadic Parkinson’s Disease in a Han Chinese Population - Hong Pan; Jun-Yi Shen; Juan-Juan Du; Shi-Shuang Cui; Jin Liu; Yi-Qi Lin; Yi-Xi He; Yang Fu; Chao Gao; Gen Li; Sheng-Di Chen; Jian-Fang Ma (Neuroscience Bulletin, 2018)

Metabolic fate of glucose in the brain of APP/PS1 transgenic mice at 10 months of age: a 13C NMR metabolomic study - Qi Zhou; Hong Zheng; Jiuxia Chen; Chen Li; Yao Du; Huanhuan Xia; Hongchang Gao (Metabolic Brain Disease, 2018)

Social Isolation During Adolescence Induces Anxiety Behaviors and Enhances Firing Activity in BLA Pyramidal Neurons via mGluR5 Upregulation - Song Lin; Xin Li; Yi-Hua Chen; Feng Gao; Hao Chen; Neng-Yuan Hu; Lang Huang; Zheng-Yi Luo; Ji-Hong Liu; Qiang-Long You; Ya-Nan Yin; Ze-Lin Li; et al. (Molecular Neurobiology, 2018)

Warming‐induced upward migration of the alpine treeline in the Changbai Mountains, northeast China - Haibo Du; Jie Liu; Mai‐He Li; Ulf Büntgen; Yue Yang; Lei Wang; Zhengfang Wu; Hong S. He (Global Change Biology, 2018)
Treeline responses to environmental changes describe an important phenomenon in global change research. Often conflicting results and generally too short observations are, however, still challenging our understanding of climate‐induced treeline dynamics. Here, we use a state‐of‐the‐art dendroecological approach to reconstruct long‐term changes in the position of the alpine treeline in relation to air temperature at two sides in the Changbai Mountains in northeast China. Over the past 160 years, the treeline increased by around 80 m, a process that can be divided into three phases of different rates and drives. The first phase was mainly influenced by vegetation recovery after an eruption of the Tianchi volcano in 1702. The slowly upward shift in the second phase was consistent with the slowly increasing temperature. The last phase coincided with rapid warming since 1985, and shows with 33 m per 1°C, the most intense upward shift. The spatial distribution and age structure of trees beyond the current treeline confirm the latest, warming‐induced upward shift. Our results suggest that the alpine treeline will continue to rise, and that the alpine tundra may disappear if temperatures will increase further. This study not only enhances mechanistic understanding of long‐term treeline dynamics, but also highlights the effects of rising temperatures on high‐elevation vegetation dynamics.

Inducible ATF3–NFAT axis aggravates podocyte injury - Hong Zhang; Shun Liang; Yue Du; Ruizhao Li; Chaosheng He; Wenjian Wang; Shuangxin Liu; Zhiming Ye; Xinling Liang; Wei Shi; Bin Zhang (Journal of Molecular Medicine, 2018)

Isolation, selection, and biological characterization research of highly effective electricigens from MFCs for phenol degradation - Guo Wei; Du Xia; Wang Li-Li; Yan Hong (Folia Microbiologica, 2018)

Role of Microglia in Neurological Disorders and Their Potentials as a Therapeutic Target - Li Du; Ying Zhang; Yang Chen; Jie Zhu; Yi Yang; Hong-Liang Zhang (Molecular Neurobiology, 2017)

Two new cadinane-type sesquiterpenes from cultures of the basidiomycete Trichaptum pargamenum - Bin Tang; Xi Du; Han-An Long; Jun Du; Jian-Min Guo; Xin Hu; Hua Tu; Li Yang; Hong-Jin Liu (Natural Product Research, 2017)

Nortirucallane A, a new tirucallane-type nortriterpenoid isolated from Lonicerae japonicae flos - Xu Wang; Jing Zhang; Ya-qun Li; Bao-xiang Du; Qi-hui Sun; Yun-jiao Cao; Hai-qiang Jiang; Yu-hong Liu; Hong-lei Zhou; Rong Rong (Natural Product Research, 2017)

Cerebral Dopamine Neurotrophic Factor: A Potential Therapeutic Agent for Parkinson’s Disease - Tingting Tang; Yong Li; Qian Jiao; Xixun Du; Hong Jiang (Neuroscience Bulletin, 2017)

Activation of Transient Receptor Potential Vanilloid 4 Promotes the Proliferation of Stem Cells in the Adult Hippocampal Dentate Gyrus - Yujing Tian; Mengwen Qi; Zhiwen Hong; Yingchun Li; Yibiao Yuan; Yimei Du; Lei Chen; Ling Chen (Molecular Neurobiology, 2017)

Exploring the Potential of Naturalized Plants for Phytoremediation of Heavy Metal Contamination - Wei Fu; Kai Huang; Hong-Hong Cai; Jian Li; De-Li Zhai; Zhi-Cong Dai; Dao-Lin Du (International Journal of Environmental Research, 2017)

Enhanced dissipation of DEHP in soil and simultaneously reduced bioaccumulation of DEHP in vegetable using bioaugmentation with exogenous bacteria - Hai-Ming Zhao; Rui-Wen Hu; He-Biao Huang; Hong-Fei Wen; Huan Du; Yan-Wen Li; Hui Li; Quan-Ying Cai; Ce-Hui Mo; Jie-Sheng Liu; Ming-Hung Wong (Biology and Fertility of Soils, 2017)

Effects of the supplementation of vitamin D3 on the growth and vitamin D metabolites in juvenile Siberian sturgeon (Acipenser baerii) - Liansheng Wang; Hong Xu; Yang Wang; Chang’an Wang; Jinnan Li; Zhigang Zhao; Liang Luo; Xue Du; Qiyou Xu (Fish Physiology and Biochemistry, 2017)

Transient Receptor Potential-canonical 1 is Essential for Environmental Enrichment-Induced Cognitive Enhancement and Neurogenesis - Lai-Ling Du; Lin Wang; Xi-Fei Yang; Ping Wang; Xiao-Hong Li; Da-Min Chai; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Rong Liu; Qing Tian; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2017)

Wind and salt spray alter tree shape and dry mass density in Casuarina equisetifolia L. - Yongming Lin; Jian Li; Jonathan D. Bakker; Han Lin; Can Chen; Wei Hong; Loretta Fisher; Chengzhen Wu; Tao Hong; Haojun Deng; Guangshuai Zhang; Kun Du (Trees, 2017)

Targeted selection of Trichoderma antagonists for control of pepper Phytophthora blight in China - Yanpo Yao; Yan Li; Zhenlin Huang; Hong Yang; Changpo Sun; Jinkang Shu; Ruihuan Du; Xueliang Pang; Qi Wang (Journal of Plant Diseases and Protection, 2016)

Genetic variation in APE1 gene promoter is associated with noise-induced hearing loss in a Chinese population - Huanxi Shen; Jianrui Dou; Lei Han; Ying Bai; Qian Li; Zhiqiang Hong; Jian Shi; Hengdong Zhang; Feng Zhang; Cheng Du; Zhimin Tong; Baoli Zhu (International Archives of Occupational and Environmental Health, 2016)

Effects of Bacillus subtilis natto and Different Components in Culture on Rumen Fermentation and Rumen Functional Bacteria In Vitro - Peng Sun; Jinan Li; Dengpan Bu; Xuemei Nan; Hong Du (Current Microbiology, 2016)

Phase 1 clinical trial demonstrated that MUC1 positive metastatic seminal vesicle cancer can be effectively eradicated by modified Anti-MUC1 chimeric antigen receptor transduced T cells - Fengtao You; Licui Jiang; Bozhen Zhang; Qiang Lu; Qiao Zhou; Xiaoyang Liao; Hong Wu; Kaiqi Du; Youcai Zhu; Huimin Meng; Zhishu Gong; Yunhui Zong; et al. (Science China Life Sciences, 2016)

RpoE is a Putative Antibiotic Resistance Regulator of Salmonella enteric Serovar Typhi - Xiaofang Xie; Haifang Zhang; Yi Zheng; Aiqing Li; Min Wang; Huiqin Zhou; Xueming Zhu; Zachary Schneider; Liang Chen; Barry N. Kreiswirth; Hong Du (Current Microbiology, 2016)

The pseudorabies virus DNA polymerase processivity factor UL42 exists as a monomer in vitro and in vivo - Yi-Ping Wang; Li-Ping Huang; Wen-Juan Du; Yan-Wu Wei; De-Li Xia; Hong-Li Wu; Li Feng; Chang-Ming Liu (Archives of Virology, 2016)

Propofol Administration During Early Postnatal Life Suppresses Hippocampal Neurogenesis - Jing Huang; Sheng Jing; Xi Chen; Xiaohang Bao; Zhiyong Du; Hong Li; Tiande Yang; Xiaotang Fan (Molecular Neurobiology, 2016)

Transcriptome sequencing discovers genes related to fatty acid biosynthesis in the seeds of Eucommia ulmoides - Yan-zhi Feng; Lu Wang; Jian-min Fu; Ta-na Wuyun; Hong-yan Du; Xiao-feng Tan; Feng Zou; Fang-dong Li (Genes & Genomics, 2016)

Activation of Transient Receptor Potential Vanilloid 4 is Involved in Neuronal Injury in Middle Cerebral Artery Occlusion in Mice - Pinghui Jie; Zihong Lu; Zhiwen Hong; Lin Li; Libin Zhou; Yingchun Li; Rong Zhou; Yebo Zhou; Yimei Du; Lei Chen; Ling Chen (Molecular Neurobiology, 2016)

Mechanism of Developmental Stagnancy of Rice Inferior Spikelets at Early Grain-Filling Stage as Revealed by Proteomic Analysis - Zhixing Zhang; Jun Tang; Tingwei Du; Hong Zhao; Zhong Li; Zhou Li; Wenxiong Lin (Plant Molecular Biology Reporter, 2015)

Myeloid-Specific Blockade of Notch Signaling by RBP-J Knockout Attenuates Spinal Cord Injury Accompanied by Compromised Inflammation Response in Mice - Bei-Yu Chen; Min-Hua Zheng; Yan Chen; Yan-Ling Du; Xiao-Long Sun; Xing Zhang; Li Duan; Fang Gao; Liang Liang; Hong-Yan Qin; Zhuo-Jing Luo; Hua Han (Molecular Neurobiology, 2015)

Enzymatic hydrolysis of 7-xylosyltaxanes by an extracellular xylosidase from Cellulosimicrobium cellulans - Tong-Yi Dou; Hong-Wei Luan; Xing-Bao Liu; Shi-Yang Li; Xun-Fu Du; Ling Yang (Biotechnology Letters, 2015)

Lipoxin A4 Activates Nrf2 Pathway and Ameliorates Cell Damage in Cultured Cortical Astrocytes Exposed to Oxygen-Glucose Deprivation/Reperfusion Insults - Le Wu; Hong-Hua Li; Qiang Wu; Sen Miao; Zi-Jian Liu; Ping Wu; Du-Yun Ye (Journal of Molecular Neuroscience, 2015)

Exosomes from Dendritic Cells Loaded with Chaperone-Rich Cell Lysates Elicit a Potent T Cell Immune Response Against Intracranial Glioma in Mice - Ning Bu; Haiqin Wu; Guilian Zhang; Shuqin Zhan; Ru Zhang; Hong Sun; Yun Du; Li Yao; Huqing Wang (Journal of Molecular Neuroscience, 2015)

HMGB1 Silencing Potentiates the Anti-inflammatory Effects of Sodium Ferulate in ox-LDL-Stimulated Vascular Smooth Muscle Cells - Nan Hu; Lingshang Kong; Aimin Qian; Qingyou Meng; Chenglong Li; Xiaobin Yu; Hong Chen; Xiaolong Du; Xiaoqiang Li (Cell Biochemistry and Biophysics, 2015)

Activation of NOD1 by DAP contributes to myocardial ischemia/reperfusion injury via multiple signaling pathways - Hui Yang; Nan Li; Li-Na Song; Lei Wang; Cui Tian; Chao-Shu Tang; Jie Du; Hui-Hua Li; Xiao-Hong Yu; Hong-Xia Wang (Apoptosis, 2015)

Relationship of Blood Levels of Pb with Cu, Zn, Ca, Mg, Fe, and Hb in Children Aged 0∼6 Years from Wuhan, China - Jingping Ye; Chuang Du; Lu Wang; Zhen Li; Shaoxin Huang; Hong Wang; Liping He; Yongyi Bi; Chunhong Wang (Biological Trace Element Research, 2015)

A novel species of ellipsoidal multicellular magnetotactic prokaryotes from L ake Y uehu in C hina - Yi‐Ran Chen; Rui Zhang; Hai‐Jian Du; Hong‐Miao Pan; Wen‐Yan Zhang; Ke Zhou; Jin‐Hua Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2015)
Summary Two morphotypes of multicellular magnetotactic prokaryotes ( MMPs ) have been identified: spherical (several species) and ellipsoidal (previously one species). Here, we report novel ellipsoidal MMPs that are ∼ 10 × 8 μm in size, and composed of about 86 cells arranged in six to eight interlaced circles. Each MMP was composed of cells that synthesized either bullet‐shaped magnetite magnetosomes alone, or both bullet‐shaped magnetite and rectangular greigite magnetosomes. They showed north‐seeking magnetotaxis, ping‐pong motility and negative phototaxis at a velocity up to 300 μm s −1 . During reproduction, they divided along either their long‐ or short‐body axes. For genetic analysis, we sorted the ellipsoidal MMPs with micromanipulation and amplified their genomes using multiple displacement amplification. We sequenced the 16 S r RNA gene and found 6.9% sequence divergence from that of ellipsoidal MMPs , Candidatus Magnetananas tsingtaoensis and > 8.3% divergence from those of spherical MMPs . Therefore, the novel MMPs belong to different species and genus compared with the currently known ellipsoidal and spherical MMPs respectively. The novel MMPs display a morphological cell differentiation, implying a potential division of labour. These findings provide new insights into the diversity of MMPs in general, and contribute to our understanding of the evolution of multicellularity among prokaryotes.

Unsupervised change detection based on robust chi-squared transform for bitemporal remotely sensed images - Aiye Shi; Du Q. Huynh; Feng Chen Huang; Shao Hong Shen; Wen Ping Lu; Zhen Li Ma (International Journal of Remote Sensing, 2014)

Multiple correlations of mRNA expression and protein abundance in human cytokine profile - Hong-wu Du; Guang-yu Chen; Chun-he Yang; Chuan-bao Li; Yi-ping Xun; Jia Liu; Peng Chen; Li-li Shi (Molecular Biology Reports, 2014)

Screening for Differentially Expressed Genes in Endophytic Fungus Strain 39 During Co-culture with Herbal Extract of its Host Dioscorea nipponica Makino - Chang-Hong Ding; Xiao-Wei Du; Ying Xu; Xiao-Meng Xu; Jin-Chao Mou; Dan Yu; Jun-Kai Wu; Fan-Jia Meng; Yan Liu; Wan-Li Wang; Li-Juan Wang (Current Microbiology, 2014)

Two Chinese pedigrees for adenomatous polyposis coli: new mutations at codon 1309 and predisposition to phenotypic variations - Dai-Xiang Liao; Bing Li; Xue-Mei Du; Jun-Hui Yu; Hong Chang; Zhi-Qiang Wu; Hao-Jie Hao; You-Xin Wang; Wei-Dong Han; Shu-jun Cheng; Cheng-Hua Luo (Familial Cancer, 2014)

Molecular cloning, characterization and function analysis of a GDH gene from Sclerotinia sclerotiorum in rice - Changqing Du; Jianzhong Lin; Yuanzhu Yang; Hong Liu; Chiyu Li; Yanbiao Zhou; Yixing Li; Dongying Tang; Xiaoying Zhao; Yonghua Zhu; Xuanming Liu (Molecular Biology Reports, 2014)

Transcript suppression of TaGW2 increased grain width and weight in bread wheat - Yantao Hong; Longfei Chen; Li-pu Du; Zhenqi Su; Jinfen Wang; Xingguo Ye; Lin Qi; Zengyan Zhang (Functional & Integrative Genomics, 2014)

Nuclear factor-κB signaling pathway is involved in phospholipase Cε-regulated proliferation in human renal cell carcinoma cells - Hong-fei Du; Li-ping Ou; Xue-dong Song; Yan-ru Fan; Xue Yang; Bing Tan; Zhen Quan; Chun-Li Luo; Xiao-hou Wu (Molecular and Cellular Biochemistry, 2014)

Inhibition of 12/15 lipoxygenase by baicalein reduces myocardial ischemia/reperfusion injury via modulation of multiple signaling pathways - Lina Song; Hui Yang; Hong-Xia Wang; Cui Tian; Yu Liu; Xiang-Jun Zeng; Erhe Gao; Yu-Ming Kang; Jie Du; Hui-Hua Li (Apoptosis, 2014)

Near-Infrared Light-Sensitive Liposomes for the Enhanced Photothermal Tumor Treatment by the Combination with Chemotherapy - Jian You; Peizun Zhang; Fuqiang Hu; Yongzhong Du; Hong Yuan; Jiang Zhu; Zuhua Wang; Jialin Zhou; Chun Li (Pharmaceutical Research, 2014)

HIRA is essential for the development of gibel carp - Meng-Yu Wang; Qiu-Hong Guo; Xin-Zheng Du; Li Zhou; Qian Luo; Qiao-Hui Zeng; Jia-Lin Wang; Hao-Bin Zhao; Yu-Feng Wang (Fish Physiology and Biochemistry, 2014)

Artificial antigen synthesis and the development of polyclonal antibody-based immunoassay for citreoviridin determination - Zhen Hong Zhuang; Shan Jin Que; Yue Ming Gao; Jun Yuan; Zhou Ye; Min Du; Guang Mei Lin; Li Cai Liu; Shi Hua Wang (World Journal of Microbiology and Biotechnology, 2014)

A novel peroxinectin involved in antiviral and antibacterial immunity of mud crab, Scylla paramamosain - Zhi-Qiang Du; Qian Ren; An-Ming Huang; Wen-Hong Fang; Jun-Fang Zhou; Lu-Jiao Gao; Xin-Cang Li (Molecular Biology Reports, 2013)

Effect of sulphate nutrition on arsenic translocation and photosynthesis of rice seedlings - Rui Song; Chen-Yun Zhao; Juan Liu; Jing Zhang; Yan-Xiu Du; Jun-Zhou Li; Hong-Zheng Sun; Hong-Bing Zhao; Quan-Zhi Zhao (Acta Physiologiae Plantarum, 2013)

Association Between Neurotensin Receptor 1 Gene Polymorphisms and Alcohol Dependence in a Male Han Chinese Population - Hui Ma; Yinglin Huang; Bo Zhang; Yuan Wang; Hong Zhao; Hong Du; Zhengtu Cong; Jingying Li; Gang Zhu (Journal of Molecular Neuroscience, 2013)

Activating transcription factor 4 is involved in endoplasmic reticulum stress-mediated apoptosis contributing to vascular calcification - Xiao-Hui Duan; Jin-Rui Chang; Jing Zhang; Bao-Hong Zhang; Yu-Lin Li; Xu Teng; Yi Zhu; Jie Du; Chao-Shu Tang; Yong-Fen Qi (Apoptosis, 2013)

Proximal tubule specific knockout of the Na+/H+ exchanger NHE3: effects on bicarbonate absorption and ammonium excretion - Hong C. Li; Zhaopeng Du; Sharon Barone; Isabelle Rubera; Alicia A. McDonough; Michel Tauc; Kamyar Zahedi; Tong Wang; Manoocher Soleimani (Journal of Molecular Medicine, 2013)

Verapamil reverses cardiac iron overload in streptozocin-induced diabetic rats - Hong-li Shan; Yan Wang; Jian-wei Wu; Peng-zhou Hang; Xin Li; Li-hua Sun; Jian-cui Qi; Yu-ying Mao; Zhi-dan Sun; Zhi-min Du (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Reduction of methylviologen-mediated oxidative stress tolerance in antisense transgenic tobacco seedlings through restricted expression of StAPX - Wei-hong Sun; Yong Wang; Hua-gang He; Xue Li; Wan Song; Bin Du; Qing-wei Meng (Journal of Zhejiang University-SCIENCE B, 2013)

Edaravone Ameliorates Oxidative Damage Associated with Aβ25-35 Treatment in PC12 Cells - Gui-lian Zhang; Wang-gang Zhang; Yun Du; Li Yao; Hong Sun; Ru Zhang; Enqi Liu; Ning Bu; Hai-qin Wu; Lei Zhang; Ting-ting Li; Ying-ying Guo (Journal of Molecular Neuroscience, 2013)

Slow N-acetyltransferase 2 genotype contributes to anti-tuberculosis drug-induced hepatotoxicity: a meta-analysis - Haijian Du; Xiaorong Chen; Yi Fang; Ouyang Yan; Hong Xu; Li Li; Weifeng Li; Wenjie Huang (Molecular Biology Reports, 2013)

Development of a core set of single-locus SSR markers for allotetraploid rapeseed (Brassica napus L.) - Haitao Li; Muhammad Younas; Xiaofeng Wang; Xuemin Li; Lin Chen; Bo Zhao; Xun Chen; Jinsong Xu; Fan Hou; Baohua Hong; Gang Liu; Hongyang Zhao; et al. (Theoretical and Applied Genetics, 2013)

Morphological and molecular cytogenetic characterization of partial octoploid Tritileymus - Jing Wang; Xin-Hong Chen; Wan-Li Du; Ji-Xin Zhao; Jun Wu; Xue-Ni Cheng; Yu-Hui Pang; Qun-Hui Yang; Shu-Hui Liu; Jie Fu (Genetic Resources and Crop Evolution, 2013)

Potential Prevention and Treatment of Maifanite for Alzheimer's Disease Based on Behavior Test, Oxidative Stress Assay, and Trace Element Analysis in Hippocampus of Aβ(25–35)-Induced AD Rats - Ling-Feng Jiang; Hai-Lin Liao; Hong-Miao Huang; Li-Xia Zhou; Ling Li; Shi-Xian Cheng; Cheng-Zhi Du (Biological Trace Element Research, 2013)

TNFAIP3 gene polymorphisms confer risk for Behcet’s disease in a Chinese Han population - Hong Li; Qing Liu; Shengping Hou; Liping Du; Qingyun Zhou; Yan Zhou; Aize Kijlstra; Zheng Li; Peizeng Yang (Human Genetics, 2013)

Development and identification of a wheat-Leymus mollis multiple alien substitution line - Ji-Xin Zhao; Wan-Li Du; Jun Wu; Xue-Ni Cheng; Yang Gao; Yu-Hui Pang; Xin-Hong Chen; Shu-Hui Liu; Qun-Hui Yang; Jie Fu (Euphytica, 2013)

The TRIMCyp genotype in four species of macaques in China - Chang-Qing Yu; Lei Na; Xiao-Ling Lv; Jian-Dong Liu; Xiao-Ming Liu; Fang Ji; Yong-Hui Zheng; Hong-Li Du; Xian-Gang Kong; Jian-Hua Zhou (Immunogenetics, 2013)

Methylglyoxal Induces Tau Hyperphosphorylation via Promoting AGEs Formation - Xiao-Hong Li; Jia-Zhao Xie; Xia Jiang; Bing-Ling Lv; Xiang-Shu Cheng; Lai-Ling Du; Jia-Yu Zhang; Jian-Zhi Wang; Xin-Wen Zhou (NeuroMolecular Medicine, 2012)

Phylogenetic Diversity of Nitrogen Fixation Genes in the Intestinal Tract of Reticulitermes chinensis Snyder - Xin Du; Xiaojuan Li; Yin Wang; Jianxin Peng; Huazhu Hong; Hong Yang (Current Microbiology, 2012)

Primary culture of hemocytes from Eriocheir sinensis and their immune effects to the novel crustacean pathogen Spiroplasma eriocheiris - Tingming Liang; Hong Ji; Jie Du; Jiangtao Ou; Wenjie Li; Ting Wu; Qingguo Meng; Wei Gu; Wen Wang (Molecular Biology Reports, 2012)

Pseudomonas nitritireducens sp. nov., a nitrite reduction bacterium isolated from wheat soil - Ya-Nan Wang; Wei-Hong He; Hua He; Xun Du; Bin Jia; Zhi-Peng Zeng; Ming-Li An; Guo-Can Chen (Archives of Microbiology, 2012)

Lipoxin A4 Inhibits 5-Lipoxygenase Translocation and Leukotrienes Biosynthesis to Exert a Neuroprotective Effect in Cerebral Ischemia/Reperfusion Injury - Le Wu; Sen Miao; Lin-Bing Zou; Ping Wu; Hua Hao; Ke Tang; Pan Zeng; Jing Xiong; Hong-Hua Li; Qiang Wu; Lei Cai; Du-Yun Ye (Journal of Molecular Neuroscience, 2012)

Choline inhibits angiotensin II-induced cardiac hypertrophy by intracellular calcium signal and p38 MAPK pathway - Shu Wang; Hong-mei Han; Zhen-wei Pan; Peng-zhou Hang; Li-hua Sun; Ya-nan Jiang; Hao-xin Song; Zhi-min Du; Yan Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Identification of a pou2 ortholog in Chinese sturgeon, Acipenser sinensis and its expression patterns in tissues, immature individuals and during embryogenesis - Huan Ye; Hao Du; Xi-Hua Chen; Hong Cao; Tao Liu; Chuang-Ju Li (Fish Physiology and Biochemistry, 2012)

At-line monitoring of key parameters of nisin fermentation by near infrared spectroscopy, chemometric modeling and model improvement - Wei-Liang Guo; Yi-Ping Du; Yong-Can Zhou; Shuang Yang; Jia-Hui Lu; Hong-Yu Zhao; Yao Wang; Li-Rong Teng (World Journal of Microbiology and Biotechnology, 2012)

Effect of long-term administration of dietary β-1,3-glucan on growth, physiological, and immune responses in Litopenaeus vannamei (Boone, 1931) - Hong-Xia Zhao; Jun-Ming Cao; An-Li Wang; Zhen-Yu Du; Chao-Xia Ye; Yan-Hua Huang; Han-Bing Lan; Ting-Ting Zhou; Guo-Li Li (Aquaculture International, 2012)

Endogenous hydrogen peroxide is a key factor in the yeast extract-induced activation of biphenyl biosynthesis in cell cultures of Sorbus aucuparia - Xiaofang Qiu; Caiyan Lei; Lili Huang; Xing Li; He Hao; Zhigao Du; Hong Wang; Hechun Ye; Ludger Beerhues; Benye Liu (Planta, 2012)

Overexpression of osteopontin in hepatocellular carcinoma and its relationships with metastasis, invasion of tumor cells - Fan Lin; YuYuan Li; Jie Cao; ShaoFeng Fan; JiFeng Wen; GuangHui Zhu; Hong Du; YanXiao Liang (Molecular Biology Reports, 2011)

Accurate assessment of antibiotic susceptibility and screening resistant strains of a bacterial population by linear gradient plate - YuQing Liu; JingRan Li; JiaFa Du; Ming Hu; Hua Bai; Jing Qi; Chao Gao; TianTian Wei; Hong Su; JianLing Jin; PeiJi Gao (Science China Life Sciences, 2011)

Study on the Evolution of the Environment Factors for Earth Geology in Developing Project - Li Hui; Zhen-hong Yang; Li-li Du (Geotechnical and Geological Engineering, 2011)

Development of a transgenic zebrafish model expressing GFP in the notochord, somite and liver directed by the hfe2 gene promoter - Yue-Hong Bian; Cheng Xu; Junling Li; Jin Xu; Hongwei Zhang; Shao Jun Du (Transgenic Research, 2011)

Metabolic engineering of artemisinin biosynthesis in Artemisia annua L. - Benye Liu; Hong Wang; Zhigao Du; Guofeng Li; Hechun Ye (Plant Cell Reports, 2011)

Characterization of the major histocompatibility complex class II DOB, DPB1, and DQB1 alleles in cynomolgus macaques of Vietnamese origin - Fei Ling; Li-qiong Wei; Tao Wang; Hai-bo Wang; Min Zhuo; Hong-li Du; Ju-fang Wang; Xiao-ning Wang (Immunogenetics, 2011)

Seismic noise attenuation using nonstationary polynomial fitting - Guo-Chang Liu; Xiao-Hong Chen; Jing-Ye Li; Jing Du; Jia-Wen Song (Applied Geophysics, 2011)

Efficacy and safety of escitalopram versus citalopram in major depressive disorder: a 6-week, multicenter, randomized, double-blind, flexible-dose study - Jian-Jun Ou; Guang-Lei Xun; Ren-Rong Wu; Le-Hua Li; Mao-Sheng Fang; Hong-Geng Zhang; Shi-Ping Xie; Jian-Guo Shi; Bo Du; Xue-Qin Yuan; Jing-Ping Zhao (Psychopharmacology, 2011)

Analysis of bacterial communities in rhizosphere soil of healthy and diseased cotton (Gossypium sp.) at different plant growth stages - Yan Zhang; Bing-Hai Du; Zhi-gang Jin; Zheng-hua Li; Hong-ning Song; Yan-Qin Ding (Plant and Soil, 2011)

Evaluation of the hepatoprotective and antioxidant activities of Rubus parvifolius L. - Jie Gao; Cui-rong Sun; Jie-hong Yang; Jian-mei Shi; Yue-guang Du; Yu-yan Zhang; Jin-hui Li; Hai-tong Wan (Journal of Zhejiang University-SCIENCE B, 2011)

Effects of intercropping with aromatic plants on the diversity and structure of an arthropod community in a pear orchard - Bei Zhou Song; Hong Ying Wu; Yun Kong; Jie Zhang; Yan Li Du; Jing Hui Hu; Yun Cong Yao (BioControl, 2010)

The gene structure and promoter region of the vaccine target aminopeptidase H11 from the blood-sucking nematode parasite of ruminants, Haemonchus contortus - Qian-Jin Zhou; Hong-Li Zhang; Xiao-Lei Jiang; Ai-Fang Du (Functional & Integrative Genomics, 2010)

Morphological changes of Fusarium oxysporum induced by CF66I, an antifungal compound from Burkholderia cepacia - Xin Li; Hui-Ying Yu; Yi-Feng Lin; Hong-Mei Teng; Lei Du; Guo-Gang Ma (Biotechnology Letters, 2010)

Geniposide inhibits interleukin-6 and interleukin-8 production in lipopolysaccharide-induced human umbilical vein endothelial cells by blocking p38 and ERK1/2 signaling pathways - Hong-Tao Liu; Jun-Lin He; Wen-Ming Li; Zhu Yang; Ying-Xiong Wang; Juan Yin; Yu-Guang Du; Chao Yu (Inflammation Research, 2010)

GmRFP1 encodes a previously unknown RING-type E3 ubiquitin ligase in Soybean (Glycine max) - Qiu-Li Du; Wen-Zhuo Cui; Chun-Hong Zhang; De-Yue Yu (Molecular Biology Reports, 2010)

Leaf Wilting Movement Can Protect Water-Stressed Cotton (Gossypium hirsutum L.) Plants Against Photoinhibition of Photosynthesis and Maintain Carbon Assimilation in the Field - Ya-Li Zhang; Hong-Zhi Zhang; Ming-Wei Du; Wei Li; Hong-Hai Luo; Wah-Soon Chow; Wang-Feng Zhang (Journal of Plant Biology, 2010)

Production and cytogenetic characterization of intertribal somatic hybrids between Brassica napus and Isatis indigotica and backcross progenies - Xue-zhu Du; Xian-hong Ge; Xing-cheng Yao; Zhi-gang Zhao; Zai-yun Li (Plant Cell Reports, 2009)

Reversal of coenzyme specificity and improvement of catalytic efficiency of Pichia stipitis xylose reductase by rational site-directed mutagenesis - Qi-Kai Zeng; Hong-Li Du; Jing-Fang Wang; Dong-Qing Wei; Xiao-Ning Wang; Yi-Xue Li; Ying Lin (Biotechnology Letters, 2009)

Genetic and histological characterization of a novel recessive genic male sterile line of Brassica napus derived from a cross with Capsella bursa-pastoris - Hai-Feng Chen; Xian-Hong Ge; Xue-Zhu Du; Zhi-Gang Zhao; Zai-Yun Li (Euphytica, 2009)

QTLs of cold tolerance-related traits at the booting stage for NIL-RILs in rice revealed by SSR - Yawen Zeng; Shuming Yang; Hong Cui; Xiaojuan Yang; Liming Xu; Juan Du; Xiaoying Pu; Zichao Li; Zaiquan Cheng; Xingqi Huang (Genes & Genomics, 2009)

Digenic inheritance of non-syndromic deafness caused by mutations at the gap junction proteins Cx26 and Cx31 - Xue-Zhong Liu; Yongyi Yuan; Denise Yan; Emilie Hong Ding; Xiao Mei Ouyang; Yu Fei; Wenxue Tang; Huijun Yuan; Qing Chang; Li Lin Du; Xin Zhang; Guojian Wang; et al. (Human Genetics, 2009)

Synergistic up-regulation of muscle LIM protein expression in C2C12 and NIH3T3 cells by myogenin and MEF2C - Zhen-Xing Ji; Chao Du; Guo-Sheng Wu; Shu-Yan Li; Guo-Shun An; Yu-Xi Yang; Ru Jia; Hong-Ti Jia; Ju-Hua Ni (Molecular Genetics and Genomics, 2009)

Production and characterization of intergeneric somatic hybrids between Brassica napus and Orychophragmus violaceus and their backcrossing progenies - Zhi-gang Zhao; Ting-ting Hu; Xian-Hong Ge; Xue-zhu Du; Li Ding; Zai-yun Li (Plant Cell Reports, 2008)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Molecular Cloning, Mapping, and Polymorphism of the Porcine SCG2 gene - Hong-Li Du; Jing Chen; Yu-Shan Zhang; Xi-Quan Zhang (Biochemical Genetics, 2008)

Chromosome elimination and fragment introgression and recombination producing intertribal partial hybrids from Brassica napus × Lesquerella fendleri crosses - Xue-Zhu Du; Xian-Hong Ge; Zhi-Gang Zhao; Zai-Yun Li (Plant Cell Reports, 2008)

A follow-up study of mortality among the arseniasis patients exposed to indoor combustion of high arsenic coal in Southwest Guizhou Autonomous Prefecture, China - Ji-gang Chen; Yu-gang Chen; Yun-shu Zhou; Guo-fang Lin; Xiu-jie Li; Chao-gang Jia; Wei-chao Guo; Hui Du; Hong-chao Lu; Hong Meng; Xin-jiang Zhang; Klaus Golka; et al. (International Archives of Occupational and Environmental Health, 2007)

Crossover randomized controlled trial of the electronic version of the Chinese SF-36 - Tian-hui Chen; Lu Li; Joerg M. Sigle; Ya-ping Du; Hong-mei Wang; Jun Lei (Journal of Zhejiang University-SCIENCE B, 2007)

N2O Emissions under Different Moisture and Temperature Regimes - Han Jian-gang; Zhu Yong-li; Bai Hong-ying; Qu Dong; Chu Jin-yu; Wu Chun-du (Bulletin of Environmental Contamination and Toxicology, 2007)

Petrogenesis of the Pt–Pd mineralized Jinbaoshan ultramafic intrusion in the Permian Emeishan Large Igneous Province, SW China - Yan Tao; Chusi Li; Ruizhong Hu; Edward M. Ripley; Andao Du; Hong Zhong (Contributions to Mineralogy and Petrology, 2007)

Microbiological Characteristics of Medically Important Trichosporon Species - Hou-Min Li; Hong-Tao Du; Wei Liu; Zhe Wan; Ruo-Yu Li (Mycopathologia, 2005)

Detection of foot-and-mouth virus antibodies using a purified protein from the high-level expression of codon-optimized, foot-and-mouth disease virus complex epitopes in Escherichia coli - Houhui Song; Weihuan Fang; Zhiliang Wang; Dongxia Zheng; Jian Du; Hong Li; Yong Li; Bingsheng Qiu (Biotechnology Letters, 2004)

Evidence of a founder effect for the 235delC mutation of GJB2 (connexin26) in east Asians - Denise Yan; Hong-Joon Park; Xiao Mei Ouyang; Arti Pandya; Katsumi Doi; Raadnabazar Erdenetungalag; Li Lin Du; Naoki Matsushiro; Walter E. Nance; Andrew J. Griffith; Xue Zhong Liu (Human Genetics, 2003)